Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

Deposition distribution and optimization of a vertical three-zone counter-spraying device for greenhouse tomatoes - Zhongqing Sun; Yonghua Zhang; Liangchun Qi; Yumei Tang; Pei Wang; Zhenglin Liu; Linlin Yang; Xiuying Tang (Crop Protection, 2026)

Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effect of surface water-groundwater exchange on heavy metal transport in the vegetated rivers - Linlin Li; Jiahao Zou; Hang Li; Jiadong He; Hao Zhang; Canyong Li (Journal of Contaminant Hydrology, 2026)

The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Mechanistic insights into the oxidative dissolution and structural transformation of humic acid in carbonaceous gold ores under pressure oxidation - Yue Qi; Hongying Yang; Linlin Tong; Huiqun Niu; Shiqi Zhang (Minerals Engineering, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Boosting CO₂ sequestration and lipid production in microalgae via a dual-ligand MOF bio-hybrid strategy - Longfei Yuan; Mengwei Li; Xinqing Gao; Manrong Wu; Yitong Wu; Yiming Li; Jianjun Liao; Ping Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Effects of sorghum variety on fermentation microecology and flavor characteristics of sesame-flavor Baijiu - Guihu Zhang; Jiaxin Tang; Chunyan Liu; Linlin Liu; Deyi Zhao; Yansong Xue; Bei-Zhong Han (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Role of intraseasonal and interannual processes in ocean heat content anomalies east of Mindanao - Zhen Li; Linlin Zhang; Mengmeng Li; Weiqi Song; Xiaoluan Yan; Tangdong Qu (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Heterogeneous reaction of NO2 with hydroxyapatite particles: Effects on phosphorus water solubility - Linlin Ye; Yan Huang; Linfeng Zhang; Panya Xu; Jingjing Wang; Chengzhu Zhu; Tong Zhu; Mingjin Wang (Atmospheric Environment, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Synergistic interaction between lead and cadmium via metal-transporter gene upregulation in mice - Tingting Zhang; Weiqin Xing; James A. Ippolito; Shuangshuang Shao; Xinjun Huang; Yongqiang Yang; Linlin Zhao; Yongxia Cheng; Liping Li (BioMetals, 2026)
This study investigated the potential synergistic interactions between Pb and Cd, and assessed the contribution of transporter gene expression to the synergism. Mice were administered varying doses of Pb (15, 30 and 108 mg kg −1 ) or Cd (1, 2 and 3 mg kg −1 ), or a combination of both in the feed. Liver, kidney and bone samples were analyzed for Cd, Pb, Cu, Mn, Zn and Fe concentrations. For treatments exhibiting synergistic effects, the relative expression levels of the divalent metal transporter 1 ( Dmt1 ), ZRT-IRE-like protein 8 ( Zip8 ) and Zip14 were quantified in the liver and kidney using Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR). At 108 mg kg −1 Pb , increasing Cd doses from 0 to 1 mg kg −1 significantly increased Pb concentrations in the kidney, liver and bone by 10.6, 60.2 and 19.6%, respectively; concurrently, the relative expression of the Zip8 in the kidney increased by 69.5%, while Dmt1 and Zip14 expression in the liver increased by 79.0 and 85.6%, respectively. At Cd doses ≥ 1 mg kg −1 , increasing Pb rate resulted in elevated Cd concentrations in the kidney, liver and bone; however, no significant changes in transporter expression levels were observed in the kidney under these treatments, possibly due to the upregulation of transporter genes in the intestines. Results demonstrate that interactions between Pb and Cd can be synergistic, and upregulation of certain transporter genes were responsible for such synergism. These findings offer important insights for mitigating the health risks associated with heavy metal exposure in animal and humans.

Optimal grasping direction of a flexible gripper and its RGB-D multimodal estimation method - Jingwei Sun; Linlin Sun; Shuangxi Liu; Huawei Yang; Zixu Chen; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

A YjiC-like UDP-glycosyltransferase CtYjiC regulates melanization, infection-related development and virulence in Colletotrichum truncatum - Yulin Qian; Xiaoying Zhai; Qinyi Wang; Jun Liu; Linlin Zhang; Yaxin Zhang; Chunzhi Jin; Long Jin; Kee-Sun Shin; Qin Xiong (Physiological and Molecular Plant Pathology, 2026)

Excitation force in a two-stage pump-jet propulsor: The modulation effect via the rotor phase angle - Jiansheng Zhang; Linlin Cao; Min Chai; Dazhuan Wu; Shuihua Zheng (Ocean Engineering, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Glycated walnut protein linseed gum conjugates for HIPE-based dressing - Bin Zhang; Li Yang; Xia Chen; Ziyi Liao; Linlin Hou; Kai Zheng; Congfang Li; Juan Dong (Journal of Food Engineering, 2026)

Tackling antibiotic resistance genes as environmental contaminants: Innovations in advanced oxidation processes and strategic solutions - Chen Gao; Liang Zhang; Linlin Zang; Hian Kee Lee; Sheng Tang (Journal of Environmental Sciences, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

Rural domestic waste generation characteristics and treatment-related greenhouse gas emissions: A case study of Guangdong Province, China - Yao He; Jie Zhang; Chen Lin; Linlin Xia; Yazhuo Wang; Hewen Zhou; Xun-an Ning (Environmental Pollution, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

VHGAE: Drug-Target Interaction Prediction Model Based on Heterogeneous Graph Variational Autoencoder - Chen Zhang; Jiaqi Sun; Linlin Xing; Longbo Zhang; Hongzhen Cai; Kai Che (Interdisciplinary Sciences: Computational Life Sciences, 2026)

IGF1-IGF1R signaling in tumor-associated macrophages regulates extracellular matrix organization in BRAF inhibitor-targeted melanoma - Ya Luo; Linlin Liu; Xing Zhou; Jiao Yang; Min Tang; Wei Feng; Chunlan Du; Xiaobo Liu; Liu Yang; Fei Liu; Liqun Zhang (Molecular and Cellular Biochemistry, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Ambient-temperature hydrogen storage kinetics of magnesium-based composites enabled by acetone-assisted ball milling and TiF3 catalysis - Linlin Zhang; Qingyun Shi; Chunmin Zhang; Bingbing Chen; Chunli Wang; Limin Wang; Yong Cheng (Fuel, 2026)

Gel-based fascia analogs from soy lipophilic protein and 11S globulin for connective tissue simulation in plant-based meat - Jiyuan Liu; Yixin Zhang; Linlin Liu; Ying Zhu; Yang Li; Mingshou Lv; Bingyu Sun; Xiuqing Zhu; Lianzhou Jiang; Yuyang Huang (Food Bioscience, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Interdecadal change in triggering effect of subtropical Indian Ocean dipole on tropical Indian Ocean dipole and the role of Southern annular mode - Junqiao Feng; Linlin Zhang; Fujun Wang (Climate Dynamics, 2026)

Genesis of Successive Quasi-Linear Convective Systems over North China: Dynamical and Thermodynamic Forcing by a Cold Vortex, Complex Terrain, and Surface Boundaries - Yan Zhang; Rudi Xia; Jinfang Yin; Jianhua Sun; Linlin Zheng (Journal of Meteorological Research, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

Clinical and Molecular Characterization of Five Additional Individuals With SATB2-Associated Syndrome in Guangxi - Sheng Yi; Qinle Zhang; Fei Chen; Xunzhao Zhou; Qiang Zhang; Shang Yi; Xiaofei Zhang; Jiale Qian; Linlin Wang; Shujie Zhang; Biyan Chen; Zailong Qin; et al. (Biochemical Genetics, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Progressive Failure Behavior of Fracture-Grouted Sandstone After High-Temperature Treatment During Uniaxial Loading: Insights from AE-DIC Experiments and Grain-Based Cohesive Modeling - Haoyang Zhang; Annan Jiang; Fu Zheng; Linlin Liu; Minghao Hao (Rock Mechanics and Rock Engineering, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Co-adaptive dynamics of human activity and crop Climatic Niches in the Neolithic Wei River Valley, China (8000–4000 cal. BP) - Xiang Jinhui; Shao Bingxin; Zhou Mile; Wang Yanpeng; Zhai Linlin; Chen Honghai; Zhang Gaike; Ma Zhikun (Quaternary Science Reviews, 2026)

Mechanisms of broadband force generation and efficient prediction for a pump-jet propulsor - Jianwei Zhang; Xinli Jin; Jianping Cheng; Duo Xiang; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

Numerical simulation and improvement of the temperature rise evolution during the Cryo-compressed hydrogen filling process in type III vessels - Linlin Gao; Haocheng Wang; Bo Tang; Teng Zhang; Xueqiang Dong; Maoqiong Gong (International Journal of Refrigeration, 2026)

Lactobacillus paracasei PC18 fermentation enhances the functional and hypoglycemic properties of soluble dietary fiber from lotus root residue. - Hongzhi Zhang; Lingyu Li; Anthony Pius Bassey; Zhiwei Fu; Yongsheng Zhu; Kaiyan Liu; Linlin Fan; Xiaoli Liu (Food Research International, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Triggering Effect of Indian Ocean Dipole on Subtropical Indian Ocean Dipole: Interdecadal Change and Modulation by Interdecadal Pacific Oscillation - Junqiao Feng; Linlin Zhang; Fujun Wang (International Journal of Climatology, 2026)
Based on observational and reanalysis datasets, this study examines the relationship between the tropical Indian Ocean Dipole (IOD) that matures in boreal autumn and the subsequent Subtropical Indian Ocean Dipole (SIOD) that occurs in the following boreal winter, as well as its interdecadal variability over 1960–2024. Results suggest that a significant correlation between IOD and SIOD only exists in 1979–2005. During this strong correlation period, an intense IOD can trigger a persistent meridional circulation and mid‐latitude Rossby wave train, maintaining an anomalous cyclone–anticyclone pair (CACP) over the subtropical Indian Ocean, with the cyclone in the west and the anticyclone in the east, ultimately leading to the development of SIOD via local air–sea coupling. In other periods, this relationship weakens and the described coupling pathway fails to establish. A key factor enabling this efficient cross‐seasonal linkage is the presence of sustained oceanic memory. Specifically, the sea surface temperature and subsurface heat anomalies associated with the IOD persist from boreal autumn into winter, providing a thermal precondition that interacts with the atmospheric circulation to eventually develop the SIOD. Further analysis indicates that this interdecadal variation is modulated by the Interdecadal Pacific Oscillation (IPO). Specifically, the positive phase of IPO strengthens the Indo–Pacific Walker circulation anomaly, reinforces the tropical–subtropical meridional pathway, and thereby enhances the IOD's triggering effect on SIOD. In contrast, the negative IPO phase suppresses this pathway. This study offers new mechanistic insights that advance our understanding of cross‐seasonal interactions in the Indian Ocean and contribute to improved climate predictions. Furthermore, it clarifies the importance of accounting for non‐stationarity in the climatic background for seasonal forecasting.

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

Identification of Fertility and Internal Genetic Uniformity in Monogerm Sugar Beet Hybrid Combinations - Chengwei Zhang; Rui Gao; Gaofei Lü; Zedong Wu; Linlin Sun (Sugar Tech, 2026)

Mechanistic study of wheat straw-enhanced sulfur release and denitrification in a pyrite-based bioretention system: Iron–sulfur–carbon synergistic interactions - Zhaoyang You; Jinlong Wang; Tao Wang; Xi Chen; Yongmei Zhang; Su Li; Linlin Tong; Kinjal J. Shah (Chemosphere, 2026)

Electric vehicle usage and vehicle kilometers travelled: a literature review - Linlin Zhang; Dea van Lierop; Dick Ettema (Transportation Research Part D: Transport and Environment, 2026)

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

A coordinated control framework for maneuvering and power management in autonomous all-electric ships - Tiewei Song; Lijun Fu; Linlin Zhong; Yaxiang Fan; Meng Zhang (Ocean Engineering, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Synthesis of lead-free perovskite Z-scheme heterojunction CeO2/Cs3Bi2Br9 via in-situ growth strategy to promote photocatalytic CO2 reduction - Xiaodong Zhang; Xinyue Peng; Han Cui; Mai Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

3-mercaptopropyltriethoxysilane modified zein electrospun membrane for ethylene removal and its application to banana preservation - Feng Xiao; Yimeng Zhang; Haoran Wang; Ji Wei; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Comparison of Turbulent Transport Dissimilarity and the Role of Coherent Structures in the Unstable Surface Layer Between Urban and Rural Areas - Qiyue Sun; Lu Zhang; Jiesheng Xue; Linlin Wang; Yubin Li; Yuanjian Yang (Boundary-Layer Meteorology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Coupling MICP with hydroxypropyl trimethyl ammonium chloride chitosan-loaded zeolite for cleaner dust consolidation: Enhanced mineralization and ammonium mitigation mechanisms - Ruoxi Li; Wen Nie; Linlin Zhang; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi (Process Safety and Environmental Protection, 2026)

Extraction of tungsten and molybdenum from low-grade tungsten-molybdenum ore: Thermodynamic calculations and kinetic analyses - Jian Kang; Linlin Tong; Qin Zhang; Zhenan Jin; Han Zhao; Bin Xiong; Hongying Yang (Minerals Engineering, 2026)

Corrigendum to “China's agricultural upgrade: Digital inclusive finance driving high-quality development” [J. Rural Stud., Volume 121 (2026), 103927] - Liangen Zeng; Yuandong Zou; Yisha Fu; Yanfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

Paleozoic polyphase strain and rheological evolution of the Shangdan shear zone, Qinling Orogen, central China - Linlin Zeng; Han Zheng; Ian P. Cawood; Dexian Zhang; Shibo Han; Peixuan Kang; Guochun Zhao (Journal of Structural Geology, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Boosting electroreduction of CO2 to multicarbon products over copper/barium oxide nanocatalysts - Zhenwei Tong; Shengpan Peng; Shengwei Zhang; Linlin Wei; Rihua Xiong (Fuel, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

Probiotics as a biocontrol strategy against Salmonella in poultry: A global meta-analysis - Mingjuan Qu; Lisheng Zhang; Jianlong Zhang; Xin Yu; Linlin Jiang; Hongwei Zhu; Xingxiao Zhang (Food Control, 2026)

In-situ synergistic mechanism of wetting and biomineralization in a polymeric surfactant-based microbial composite dust suppressant for dust control in open-pit mines - Ruoxi Li; Wen Nie; Linlin Zhang; Wenjin Niu; Qifan Tian; Jin Shi (Environmental Research, 2026)

The ecological and economic impacts of national park pilot projects in China - Xiaobin Zhang; Heng Luo; Xianfan Shu; Linlin Zhang (Ecological Economics, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Similarity-based classification of groundwater hydrographs to reveal regional groundwater dynamics patterns in a semi-arid agricultural area - Xiangbo Meng; Xi Chen; Yonggen Zhang; Man Gao; Linlin Lu (Hydrogeology Journal, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

KansFormer network based on a multimodal cross-attention mechanism for drug-target interaction prediction - Anting Gao; Yuandong Liu; Kai Che; Longbo Zhang; Yifeng Gao; Linlin Xing (Molecular Diversity, 2026)

Penicinoid A, an undescribed sesterterpenoid with cytotoxic activity from Penicillium herquei - Mengyi Deng; Enrui Zhang; Fengtai Qiu; Yingying Fei; Yuyan Liu; Linlin Li; Yiyang Xiong; Xianli Zhou (Natural Product Research, 2026)

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

Synergistic strategy for enhanced bio-oxidation of refractory gold concentrate with high arsenic and sulfur: ferric oxidation with mixed organic nutrients supplementation - Shiqi Zhang; Hongying Yang; Linlin Tong; Zhenan Jin; Pengcheng Ma (Minerals Engineering, 2026)

Unlocking circularity in rural waste management in northwest China: A systematic framework to quantify energy-environment-pollution nexus - Yuansheng Huang; Linlin Wang; Yi Liu; Yihan Chen; Xinglin Zhang; Yiliang He (Journal of Cleaner Production, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

Bioaugmentation of thiourea-acclimated biomass relieves thiourea’s inhibition of nitrification - Meng Huang; Xiaobing Gao; Ning Yan; Fei Liu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Spectral reconstruction of multichannel fluorescence for rapid assessment of TVB-N in meat products - Qian You; Wenhong Gao; Zhong Han; Xin-an Zeng; Linlin Ye; Yuwen Huang; Yunqi Zhang; Ji Ma (Food Chemistry, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Advances in the understanding of spatiotemporal distribution and hazard assessment of volcanic tsunamis - Kan Zhang; Linlin Li; Peng Du; Tingting Fan; Weitao Wang; Peizhen Zhang (Science China Earth Sciences, 2026)

Mediating Effect of Self-Efficacy Between Self-Perceived Burden and End-of-Life Communication Difficulties in Cancer Patients - Yalin Zhu; Linlin Shi; Yuanyuan Jiang; Yuyan Fan; Huixian Zhang; Shouxia Chai; Yan Li (Journal of Cancer Education, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Ultrastructural Evidence of Altered Dendritic Morphology in the Prefrontal Cortex of Alzheimer's Model Rats - Jinyue Guo; Jing Liu; Yanchao Zhang; Jiazheng Liu; Hao Zhai; Linlin Li; Hua Han (Neuroscience Bulletin, 2026)

Hominin occupation of the Western Qinling Mountains as early as ∼900 ka - Zaijun Li; Jian Wang; Chongwen Luo; Yongbo Quan; Linlin Yan; Yuanxin Li; Linxueyi Wang; Shengli Yang; Jia Jia; Ziwei Tao; Tingjiang Peng; Zhenzhong Tian; et al. (Science Bulletin, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Selective separation of rare earth from acetatesolution containing aluminum by nonequilibrium extraction - Linlin Chang; Jian Li; Dongyue Xie; Xudong Liu; Yaobin Lai; Jiayi Zan; Chenjiahui Wang; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Journal of Environmental Management, 2026)

Tailoring monoglyceride oleogel crystallization by eutectic and crystal nucleation disturbance: functional frozen specialty fat for use in croissants - Yanxia An; Yi Han; Ziwei Liu; Jingyuan Su; Jian Zhang; Keke Liu; Linlin Li (Food Research International, 2026)

Advances in the effect of the structure of high-moisture extruded plant-based meat on in vitro digestive properties - Yuyang Huang; Yixin Zhang; Yang Gao; Ying Zhu; Bingyu Sun; Linlin Liu; Jiyuan Liu; Baoning Zheng; Mingshou Lv; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2026)

Oleogels in flour-based foods: an overview from the perspective of crystalline structure and functional performance - Yi Han; Linlin Li; Lukai Ma; Jingyuan Su; Yang Zhao; Jian Zhang; Yanxia An (Food Chemistry, 2026)

Chemical and sensory characteristics of Baiye No.1 (BY1H) yellow tea: Insights into flavoring mechanism and quality valuation - Shiyu Zhang; Xinzhuan Yao; Yanxia Wang; Muhammad Safiullah Virk; Shiyu Tian; Zhenkedai Yuan; Qihong Zou; Linlin Li; Shenyuan Ye; Hu Tang; Litang Lu (Food Bioscience, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

A high-order Model-free Dynamic Framework for Accurate Daily Streamflow Prediction - Jiaying Zhang; Shiqian Tang; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Water Resources Management, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

Seasonal-spatial distribution and prevailing wind analysis of Martian dust devils in Amazonis Planitia using a multi-scale attention network - Linlin Shi; Gan Liu; Jialong Lai; Xu Ma; Feifei Cui; Xiaoping Zhang; Yi Xu; Qiquan Yang (Science China Earth Sciences, 2026)

Ecological niche shapes the composition and function of microbial communities in Astragalus membranaceus - Xiao Chen; Zhengyan Li; Yaogong Zhang; Chao Yao; Yuanshuai Yu; Feifei Ding; Jingyi Xu; Yuan Li; Linlin Dong; Guangfei Wei (Plant and Soil, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

Mechanism of liver fibrosis induced by life-long triclosan exposure in offspring rats: an adverse outcome pathway framework validated by in vivo and in vitro experiments - Fu Liu; Jianing Shang; Linlin Zheng; Xiaoyu Zhang; Anqi Cui; Xue Dou; Yunwei Li; Jieyu Liu (Archives of Toxicology, 2026)

Intelligent Recognition Network for Difficult Airway Based on Multi-View Input and Attention Aggregation - Fan Zhang; Jiaqiang Zhang; Zhaoxiang Zhang; Ke Yang; Linlin Zhao; Yuelei Xu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Corrigendum to “China's agricultural upgrade: Digital inclusive finance driving high-quality development” [J. Rural Stud., Volume 121 (2026), 103927] - Liangen Zeng; Yuandong Zou; Yisha Fu; Yanfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

Influence of pore fluid on the elasto-plastic property of shales - Linghao Chen; Wanqing Shen; Shuitao Zhang; Zhilei Luo; Jianfu Shao; Linlin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Unveiling structural evolution during high-moisture extrusion of soy protein isolate-wheat gluten systems with soy dietary fiber: A sudden shutdown-based study - Ruqi Guo; Haojia Zhang; Yang Gao; Zihan Wang; Yinlin Wang; Ying Zhu; Linlin Liu; Xiuqing Zhu (Food Chemistry, 2026)

A novel bacteriophage pAEh1 for controlling Aeromonas hydrophila infection in aquaculture - Sifan Jiang; Boyang Zhou; Tongping Zhang; Rongsi Dai; Su Long; Linlin Yang; Mingwang He; YanJiao Fu; Jiajing Guo; Zhipeng Gao (Fish & Shellfish Immunology, 2026)

Meteorological observation research based on an improved EfficientNetV2 model - Haozheng Yin; Yu Cao; Linlin Liu; Dan Chen; Qiong Zhang (Environmental Modelling & Software, 2026)

Integrated multi-energy hybrid systems for net-zero buildings: Dynamic simulation, lifecycle 4E assessment, and multi-objective optimization - Manfeng Li; Mengke Liu; Guofeng Zhou; Linlin Zhang; Panpan Li; Yiji Lu (Energy and Buildings, 2026)

Enhanced selectivity for the removal of Al3+ from the simulated rare earth leachate via a 3D electrochemical hydrolysis process - Chenjiahui Wang; Jian Li; Dongyue Xie; Xudong Liu; Jiayi Zan; Linlin Chang; Yaobin Lai; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Desalination, 2026)

Black phosphorus with enhanced stability via palladium induced electronic structure modulation and its application in portable breath acetone sensing - Guangliang Li; Yunzhu Liu; Lei Ma; Hang Zhang; Jinlong Ma; Linlin Hou; Jian Duan; Guanglan Liao; Hu Long; Tielin Shi (Chemical Engineering Journal, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

Numerical Simulation of Gas Production and Geomechanical Response of Heterogeneous Gas Hydrate Reservoirs - Jiuhui Cheng; Shuitao Zhang; Linlin Wang; Guangjin Chen (Natural Resources Research, 2026)

An integrated multiscale computational study of nephrotoxicity mechanism of citrinin and its metabolites (CIMs)：density functional theory, network toxicology, and molecular dynamics simulation - Jiaxing Li; Furong Xue; Linlin Xu; Huijing Zhang; Xizi Zhang; Chenchen Qi; Chengtao Wang; Wei Chen; Di Zhang (Mycotoxin Research, 2026)

Physiological changes in carbon sequestration and lipid production characteristics of microalgae under high CO2 domestication - Xinqing Gao; Longfei Yuan; Hui Yin YEONG; Guangze Lv; Xiangya Zhang; Xiaodong Zhang; Linlin Zhang; Jianjun Liao (Environmental Science and Pollution Research, 2026)

Involvement of ARTS in bisphenol A-induced apoptosis of mouse Leydig cells - Ying Yang; Si Yang; Meijuan Zhang; Linlin Xu; Jiaxiang Chen (Toxicology, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

China's agricultural upgrade: Digital inclusive finance driving high-quality development - Liangen Zeng; Yuangdong Zou; Yisha Fu; Yangfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

Thermal performance assessment of coupled soil stratification and groundwater advection effects on vertical borehole heat exchanger - Linlin Zhang; Dongyang Fan; Yanbin Li; Tianhao Yuan; Jun Chen (Geothermics, 2026)

The effect of yeaZ on formation and resuscitation of viable but nonculturable (VBNC) Salmonella enteritidis serovar enteritidis - Yuyang Jiao; Aiqi Yang; Xin Yu; Jiayu Yu; Jianlong Zhang; Linlin Jiang; Yao Li; Yang Liu; Hongwei Zhu; Xingxiao Zhang (Food Microbiology, 2026)

Humidity-regulating antibacterial trilayer Janus membrane of polyacrylonitrile/gelatin-potato starch/polycaprolactone-cinnamon essential oil for cherry tomato preservation - Mingyi Tian; Chenlong Liu; Zhiyuan Ge; Wei Ji; Yimeng Zhang; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Preparation and application of ceramic membranes incorporating graphite tailings for oil wastewater treatment - Lixin Li; Pengyu Yan; Linlin Huang; Zhaoshun Zhan; Jun Zhang; Xinyu Li; Wei Chai; Qingju Tang; Zhurui Shen (Chemical Engineering Journal, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Convection initiation over central–eastern China: Statistics show higher frequencies over mountains with less stringent atmospheric conditions and more heterogeneous surface characteristics - Qian Wei; Jianhua Sun; Xianhong Meng; Yuanchun Zhang; Linlin Zheng; Zheng Ma (Atmospheric Research, 2026)

Bisphenol S and Neurological Health: An Integrated Overview of Neurotoxicity and Underlying Mechanisms - Xing Zhang; Linlin Wu; Dingqi Hua; Bin Zhang; Xi Wang; Linchang Li; Yi Wang; Jiangbo Zhu (Molecular Neurobiology, 2026)

Ptbp2 Alleviates Neuroinflammation and Blood–brain Barrier Disruption via Modulating Microglial Polarization in Ischemic Stroke - Wenting Xu; Linlin Li; Mengjia Zhou; Cong Zhang; Xiangjian Zhang (Molecular Neurobiology, 2026)

The Key Role of Somatostatin Neurons in the Suprachiasmatic Nucleus in Anxiety-Depression Comorbidity Following Sleep Deprivation - Yifei Zhang; Yuxin Wang; Xinyue Liu; Chunlin Ren; Ming Chen; Linlin Bi (Molecular Neurobiology, 2026)

Parental exposure to ocean acidification impacts the larval development and transcriptome of the Pacific oyster Crassostrea gigas - Hailun Fu; Wen Teng; Shoudu Zhang; Zhangjie Peng; Jiulin Chan; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Biodiversity and biogeographic patterns of Nereididae (Annelida) across the Indo-Pacific Convergence Zone - Jieyang Weng; Xuwen Wu; Tiantian Wang; Chenrui Li; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Early Palaeozoic P-T-t-D paths of the eastern Shangdan Shear Zone in Qinling Orogen, central China - Linlin Zeng; Han Zheng; Dexian Zhang; Shibo Han; Heng Peng; Peixuan Kang; Shuya Ma (International Geology Review, 2025)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

Synergistic extraction of molybdenum and tungsten from low-grade tungsten-molybdenum ores with poor flotation separability using a sodium hypochlorite-trisodium phosphate-sodium hydroxide system - Jian Kang; Linlin Tong; Qin Zhang; Han Zhao; Bin Xiong; Hongying Yang (Minerals Engineering, 2025)

Mitigating iron contamination in cyanide gold extraction: Ceramic grinding media for enhanced efficiency and reduced cyanide consumption - Qianfei Zhao; Yuhai Zhang; Peng Gao; Linlin Tong; Yuexin Han; Hongying Yang; Shuai Yuan (Minerals Engineering, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Electroenhanced organic pollutant adsorption by three - dimensional isolated electrodes: Investigation of the “short - plate effect” - Xinyu Wang; Xiaochen Zhang; Linlin Chen; Fei Yu; Jie Ma (Journal of Cleaner Production, 2025)

The gold, palladium, silver, copper, and silicon were synergistically recovered from the waste chips through the phase reconstruction and stepwise recovery methods - Shuo Liu; Yaobin Lai; Xin Chen; Jian Li; Hui Zhang; Linlin Chang; Tianyi Chen; Xuxia Zhang; Yangyang Xie; Liuyimei Yang; Tao Qi (Journal of Environmental Chemical Engineering, 2025)

Coupling hydrolyzed rice husk and ferric oxidation to enhance bio-oxidation of gold concentrate with high arsenic and sulfur - Shiqi Zhang; Hongying Yang; Linlin Tong; Zhenan Jin; Pengcheng Ma (Geochemistry, 2025)

Inhibitory effects of nisin and ε-polylysine on the microbial cell structure and physiological function of Bacillus amyloliquefaciens and applications in bread preservation - Min Qu; Xin Zhang; Xiuqing Zhu; Jingbo Kang; Linlin Liu; Mingshou Lv; Ying Zhu; Bingyu Sun (Food Bioscience, 2025)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Superior bridging effect of Pt NPs in all-solid-state Z-scheme CdS QDs/NaTaO3 microcube heterojunction for highly efficient photocatalytic hydrogen evolution - Jiayi Meng; Juhua Zhang; Yamei Huang; Zizheng Wang; Yifan Liao; Quanmei Zhou; Yuchen Wei; Linlin Gao; Wei-Lin Dai (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

NTMFF-DTA: Prediction of Drug-Target Affinity Based on Network Topology and Multi-feature Fusion - Yuandong Liu; Youzhi Liu; Haoqin Yang; Longbo Zhang; Kai Che; Linlin Xing (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Evaluation of FY-4A/4B GIIRS Atmospheric Temperature Profile Products Using Radiosonde Observations through a Per-Level Collocation Method - Xiaoyue Zhang; Yuanyuan Wang; Qiang Gong; Ying Wang; Yudi Shi; Linlin Li; Guochun Li (Journal of Meteorological Research, 2025)

How do atmospheric pollutant changes driven by anthropogenic heat provide feedback on the urban thermal environment in Beijing? - Jiangkang Qian; Linlin Zhang; Xinran Zhu; Qingyan Meng; Xinli Hu; Jianfeng Gao; Shize Chen (Sustainable Cities and Society, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

A highly sensitive and specific immunochromatographic test strip for detecting p,p′-DDA in seawater and shellfish - Teng Zhang; Yunrui Xing; Jiale Yao; Zhuan Yang; Jucai Wang; Linlin Chen; Lunguang Yao (Food Chemistry, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Seismic performance of rubberized concrete double-column piers confined by corrugated steel tubes - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Experimental study on mechanical properties of a new duplex stainless steel for structures under different temperature-stress combination paths - Shuobiao Li; Zhen Wang; Wenqi Ding; Qingzhao Zhang; Linlin Gu (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Preparation of MUF/α-ZrP@MnHP@APP composite nanolayered flame retardant coating for application on expanded polystyrene (EPS) foam - Wei Zhang; Yifu Xiang; Wantong Jiang; Zhixin Yang; Linlin Zhang; Bin Li (Chemical Engineering Journal, 2025)

Spin-polarization-enhanced photoreforming of plastic waste - Nan Zhou; Mai Zhang; Shiwei Lin; Linlin Zhang; Jianjun Liao; Chen Li; Wei Zhou (Chemical Engineering Journal, 2025)

Dynamic reversible thermochromic camouflage smart textiles for temperature visualized personal healthcare and thermal management - Weiyi Zhang; Shuo Luan; Yuyan Fang; Linlin Zhu; Yang Yang; Mingwei Tian; Lijun Qu; Tingting Fan; Jinlei Miao (Chemical Engineering Journal, 2025)

Chemical composition and mixing states of individual atmospheric particles in summer and winter: a micro-Raman spectroscopy study - Yan Huang; Qingcheng Li; Linlin Ye; Jingjing Wang; Yidan Zhang; Tong Zhu; Chengzhu Zhu; Mingjin Wang (Atmospheric Environment, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Mbnl1 Protects Against Cerebral Ischemia–Reperfusion Injury by Modulating Microglia/Macrophage Polarization via NF-κB Pathway - Wenting Xu; Mengjia Zhou; Linlin Li; Yuqing Zhang; Tianya Zhang; Xiangjian Zhang (Molecular Neurobiology, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

Topographical differentiation characteristics of double high pollution of PM2.5 and ozone in the Beijing-Tianjin-Hebei region - Huan Zhang; Xiaohong Wang; Yiheng Liang; Liyi Qin; Jinlong Li; Linlin Jiao (Air Quality, Atmosphere & Health, 2025)

MitoQ reducing sevoflurane-induced cognitive dysfunction by modulating mitochondrial dysfunction - Hengjie Su; Zhibin He; Haotian Wu; Linlin Wang; Huan Zhang; Siyi Yan (Metabolic Brain Disease, 2025)

Atypical seasonal variability of the Kuroshio Current in 2018 - Fujun Wang; Linlin Zhang; Junqiao Feng; Qingye Wang; Dunxin Hu (Frontiers in Marine Science, 2025)
Introduction Using three moorings deployed at 122.7°E, 123°E, and 123.3°E along 18°N from January 2018 to May 2020, this study investigates the seasonal variability of the Kuroshio Current (KC). Methods Sensitive experiments were conducted with the Regional Ocean Modeling System (ROMS). Results In 2019, the KC exhibited a typical seasonal cycle, being relatively strong during spring, summer, and winter, with the weakest flow occurring in autumn. In contrast, the KC displayed an atypical seasonal cycle in 2018, characterized by two distinct intraseasonal intensification events in late September and early November. The ROMS experiments revealed that local winds within the region (120°E–125°E, 15°N–20°N) were the primary driver of this atypical cycle. During the two key periods, persistent negative wind stress curl anomalies east of the mooring stations induced integrated positive sea surface height anomalies and corresponding northward meridional velocity anomalies via geostrophic balance. Discussion In 2019, the wind stress curl anomaly phases reversed compared to 2018, leading to the absence of the two peaks observed in the previous year.

A Study on Energy Loss and Transient Flow Characteristics of a Large Volute Centrifugal Pump During Power-Off Process Under Cavitation Conditions - Qingzhao Pang; Desheng Zhang; Gang Yang; Xi Shen; Qiang Pan; Linlin Geng; Qinghui Lu (Journal of Marine Science and Engineering, 2025)
A novel pumped storage system using centrifugal pumps to transfer water between reservoirs in coastal hydropower plants has significantly mitigated grid instability. However, frequent start–stop operations of large vertical centrifugal pumps, which serve as the core equipment, severely affect the operational stability of these systems. In this study, the intrinsic connection between the cavitating flow field and irreversible losses during the process was analyzed using the entropy production theory. The time–frequency characteristics of pressure pulsation in pump were analyzed by using the continuous wavelet transform. The results indicate that with the reduction in the flow rate and rotational speed, the sheet cavitation at the impeller inlet rapidly weakens until it vanishes. The cavity cavitation within the draft tube commences to emerge in the turbine mode. Separation vortices are formed due to the mismatch in the flow angle at the impeller outlet. These vortices induce local cavitation, causing both a rapid energy loss increase and high-amplitude, low-frequency pressure pulsations. During transient processes, flow instabilities induce high-amplitude, low-frequency pressure pulsations within the stay vane region, with maximum amplitude attained during runaway condition. The research results provide a theoretical foundation for the stable operation of centrifugal pumps.

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

In silico profiling of bisphenol compounds for estrogenic effects via pharmacophore modeling, molecular docking, and dynamics simulations - Lifeng Wang; Ning Li; Linlin Wang; Zengfeng Li; Qiang Li; Jiaqi Tian; Lin Zhang (Journal of Hazardous Materials, 2025)

Predictive modeling and mechanistic interpretation of single electron transfer reactivity between antibiotics and reactive halogen species - Linlin Dong; Chenxuan Zong; Jiao Qu; Fangyuan Cheng; Ya-nan Zhang (Journal of Hazardous Materials, 2025)

Rb-Sr dating of pyrite, Zircon U-Pb geochronology, and Sr-Nd-Hf isotopic geochemistry of the Baiyun Au deposit in the Qingchengzi Orefield, Liaodong Peninsula, Northeast China - Peng Zhang; Junchao Lü; Yan Zhao; Linlin Kou; Wei Pang (Journal of Geochemical Exploration, 2025)

Green methanol synthesis from renewable energy integrated with compressed CO2 energy storage and waste-based systems: Thermodynamic, economic and environmental assessment - Manfeng Li; Shipeng Yin; Guofeng Zhou; Suping Li; Bo Peng; Linlin Zhang; Tianbiao He (Journal of Cleaner Production, 2025)

Engineered ionic liquid-covalent organic framework composites for high-capacity CO₂ capture: Mechanism insights and process optimization - Shuting Zhang; Jianwen Wei; Xuequan Zou; Linlin Geng; Xiaobin Zhou (Journal of Environmental Chemical Engineering, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Amphiphilic Janus nanoparticles for effective foam fractionation of perfluorooctanoic acid (PFOA): Effect of modifier type - Yanfei Li; Zhuoxuan Zhang; Yanyan Lv; Yazhu Pei; Linlin Ding; Zhijun Zhang; Nan Hu (Environmental Research, 2025)

Molecular and physiological adaptations of Scartelaos histophorus to air exposure: Implications for amphibious fish survival - Dongdong Xiao; Ruizhi Wang; Peidong Zhang; Riyanti; Linlin Zhao; Na Song (Environmental Research, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Waste asphalt-derived hard carbon assisted by biomass templating for sodium-ion batteries - Danqing Li; Xin He; Linlin Wang; Yinghao Zhang; Xingqiao Wu; Mei Ding; Chunhui Gao; Yang Gao; Chuankun Jia (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Atmospheric boundary layer heat budget and its urban-rural differences in Beijing during a heatwave event - Qianyue Huang; Yuanjie Zhang; Jialing Xin; Yubin Li; Yue Qin; Linlin Wang (Atmospheric Research, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

Integrated transcriptome and metabolome analyses reveal regulatory mechanisms governing carbohydrate biosynthesis in Panax ginseng - Qiao Jin; Qiuxia Wang; Linlin Zhang; Yue Zhang; Zhengbo Liu (Plant Science, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Melatonin protects dopaminergic neurons in paraquat-induced Parkinson in rats through PI3K/AKT/Nrf2 pathway - Yanhui Wang; Xin Zhang; Weiliang Zhang; Minging Han; Qiang Jia; Cunxiang Bo; Hua Shao; Linlin Sai; Cheng Peng (Food and Chemical Toxicology, 2025)

Seismic behavior of prefabricated-assembled frames with corrugated steel tube confined connections and piers: Experiments, numerical models, and design - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

CRISPR/Cas9-mediated promoterless gene targeting reduces lysosome storage in MPS VII mice - Linlin Shan; Qiongyan He; Weifeng Zhang; Xiaojing Zheng; Junli Zhao; Peiyan Yang; Qinwen Mao; Haibin Xia (Science China Life Sciences, 2025)

Melatonin Promotes Cerebral Angiogenesis in Ischemic Mice via BMP6/Smad1/5/9 Pathway - Linlin Li; Yujia Yuan; Cong Zhang; Ying Li; Renhao Xu; Xiangjian Zhang; Wenyan Shang (Molecular Neurobiology, 2025)

Dissolved organic matter sources in urban outfall water before and during rainfall, indicated via its fluorescence fingerprinting - Haojie Yin; Tao Huang; Bo Wang; Yingying Zhang; Jiawei Hu; Linlin Zhu; Kaining Chen (Applied Geochemistry, 2025)

Coupled precipitation enrichment of molybdenum and tungsten for synthesizing AMTOF (artificial molybdenum and tungsten ore first) from a complex trace molybdenum-tungsten mixed solution - Han Zhao; Hongying Yang; Linlin Tong; Qin Zhang; Jiapeng Zhang (Minerals Engineering, 2025)

Mutual influence of bubble evolution and seepage flow in heterogeneous porous matrices - Linlin Gu; Shicai Sun; Rundong Zhang; Rongtao Yan; Yonghao Yin; Guanru Gong (Gas Science and Engineering, 2025)

Development of a data-driven automatic unstructured mesh generation tool suitable for compound flooding studies - Jaime R. Calzada; Y. Joseph Zhang; Fei Ye; Linlin Cui (Environmental Modelling & Software, 2025)

Flexible electrochromic film for visualized meat freshness detection - Wenhui Zhang; Wuyuan Wang; Linlin Xia; Guanghong Zhou; Jie Wang (Chemical Engineering Journal, 2025)

Engineering efficient and stable CsPbBr3 perovskite nanocrystals via multi-functional molecular mediated surface strategy toward white light-emitting devices - Hanyun Yang; Haoqi Zhu; Linlin Ma; Mengwei Luo; Hang Guo; Lepeng Zhou; Wenxu Sun; Bin Xue; Lei Zhang (Chemical Engineering Journal, 2025)

Ecological niche imprints the structure and network of microbial communities in Lonicera japonica Thunb - Zhaoyu Zhang; Yingda Dong; Xiao Chen; Guozhuang Zhang; Conglian Liang; Yuxin Zhou; Ziying Huang; Liping Shi; Shilin Chen; Linlin Dong; Guangfei Wei (Plant and Soil, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Chronological and Causal Perspectives on the Tectonic Evolution of Equatorial Atlantic - Roufida Rana Djaroun; Linlin Fan; Yanming Huang; Jinchang Zhang (Journal of Ocean University of China, 2025)

A preliminary study on the community structure of culturable planktonic and attached bacteria in the harbor of Qingdao, China - Shide Ma; Linlin Zhang; Yimeng Zhang; Yu Tai; Wen Han; Jinfeng Yang; Xin Shi; Bochao Lu; Jizhou Duan (Acta Oceanologica Sinica, 2025)

Cross-platform detection of microplastics in human biological tissues: Comparing spectroscopic and chromatographic approaches - Lin Zhang; Jiaqi Tian; Xiaodan Zhu; Linlin Wang; Xiang Yun; Liyang Liang; Shuyin Duan (Journal of Hazardous Materials, 2025)

Synergistic effects on microstructural, rheological and functional properties of starch-enhanced processed mozzarella cheese - Linlin Tang; Jialin Liu; Ke Li; Yumeng Zhang; Shaomeng Luan; Tietao Chen; Hongjuan Li; Jinghua Yu (Food Structure, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

The Physiological and Flavonoid Metabolism of the Tea Plant in Response to Nitrogen Nutrition is Regulated by the Ultraviolet-B Radiation Environment - Fang Dong; Hua Zhang; Linlin Liu; Jianyun Ruan; Meiya Liu; Qunfeng Zhang (Journal of Plant Growth Regulation, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Label-Free Direct Detection of 4MU by Plasmon Enhanced Fluorescence Sensing Based on Ag@SiO2 NPs - Liqi Wang; Xin Lv; Ziheng Song; Linlin Tian; Xinyue Du; Dong Zhang; Qingru Wang (Journal of Fluorescence, 2025)

Identification of autophagy-related biomarkers in prostate cancer prognosis - Yancheng Di; Linlin Zhao; Lingling Zhang; Lei Chen (Human Cell, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Study on the characteristics of an underwater vehicle pump-jet propeller under the influence of drag-reduction air - Xuanhao Shao; Jianwei Zhang; Haopeng Cai; Penglei Chen; Heng Liu; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

The roles of Paracoccus huijuniae for enhancing denitrification with N-methyl pyrrolidone as the electron donor - Meng Huang; Songyun Chen; Fei Liu; Haiyun Zhang; Xiaobing Gao; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Phosphorus stress disrupts leaf-root trait relationships and reduces biomass in a tropical cloud forest: Evidence from a two-year phosphorus addition experiment - Ewuketu Linger; Mengesha Asefa; Tao Zhang; Linlin Lin; Wenxing Long (Forest Ecology and Management, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Licorice water extract improves constipation by repairing the intestinal barrier and regulating the gut microbiota: A potential alternative treatment strategy - Mingwei Sun; Meng Zhao; Linlin Du; Jieying Hou; Juane Dong; Bin Zhang (Food Bioscience, 2025)

Screening of hypoglycemic and probiotic properties of Pediococcus acidilactici FM-Pa-JXM94 and exploring the potential hypoglycemic mechanism - Ying Wang; Hui Zhang; Xingna Wang; Yu Zhang; Linlin Fan; Yanhong Ma; Xiaoli Liu (Food Bioscience, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Dual-responsive gelatin/fucoidan-based membrane with colorimetric and control-released performance for meat freshness monitoring and preservation - Linlin Li; Haoran Wang; Yimeng Zhang; Wei Ji; Minmin Chen; Baocai Xu; Hualin Wang (Food Packaging and Shelf Life, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

Cover Image - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
The cover image is based on the article Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control by Zhipeng Gao et al., https://doi.org/10.1111/raq.70024 . image

Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
Aquaculture is essential for meeting future demands for food, yet it faces significant losses from infectious bacterial diseases. Aquaculture has recently been critically imperiled by the emergence of multi‐drug‐resistant bacteria, as it relies significantly on the use of antibiotics for prevention and treatment. The emergence of multidrug‐resistant bacteria poses a critical threat to aquaculture, which heavily relies on antibiotics for prevention and treatment. Bacteriophage (phage) therapy has regained attention with the spread of drug‐resistant bacteria. Phages are viruses that specifically infect bacteria and archaea. As a promising therapeutic strategy for aquatic bacterial diseases, phage therapy offers strong specificity, low resistance potential, rapid metabolism, ease of development, and cost‐effectiveness. In this review, we discuss the advantages, opportunities, and challenges of phage therapy, summarizing the status of research and highlighting emerging technologies aimed at enhancing phage therapy in aquaculture. Finally, the review looks to the future, identifying scientific and technological advances necessary to establish phage therapy as a viable and universal alternative to antibiotics in aquaculture.

Exploring Neurobiological Effects of Intermittent Theta-Burst Stimulation on the Left Cerebellum for Post-stroke Unilateral Neglect: A Preliminary Transcranial Magnetic Stimulation—Electroencephalography Investigation - Linlin Ye; Wanying Zhao; Yichen Zhang; Weiqun Song; Huanxin Xie; Lei Cao (The Cerebellum, 2025)

Prediction of landfill gases concentration based on Grey Wolf Optimization – Support Vector Regression during landfill excavation process - Zhansheng Liu; Zehua Zhang; Qingwen Zhang; Linlin Zhao (Waste Management, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

Dietary emulsifier Polysorbate 80-induced lipotoxicity promotes intestinal senescence - Linlin He; Lan Zhang; Fanyi Meng; Jingge Wei; Fei Chen; Siqi Qin; Ge Jin; Hailong Cao (Food Research International, 2025)

From field to table: Reducing residual toxicity and risk of four pesticides via washing and blanching of cowpea (Vigna unguiculata (L.) Walp.) - Shuangwei Zhang; Yajing Guo; Shanshan Zhu; Linlin Guo; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Food Chemistry, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Polystyrene microplastics (PS-MPs) harness copper presence and promote impairments in early zebrafish (Danio rerio) larvae: Developmental, biochemical, transcriptomic approaches and nontargeted metabolomics approaches - Liqiao Zhang; Dongqiu Guo; Xinrui Dong; Longxiao Liu; Mengqi Jiang; Linlin Song; Xia Wang (Environmental Research, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Huge challenges of improving ozone pollution in China: High regional background ozone concentrations calculated from observational data - Yusi Liu; Yang Zhang; Fan Yang; Linlin Liang; Guiqian Tang (Environmental Pollution, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Physiological and transcriptomic responses of the microalga Isochrysis galbana during exposure to Hg(II) stress - Linlin Zhang; Na Li; Xinfeng Xiao; Linke Guo; Wenfang Li; Yanjun Li; Fei Ling (World Journal of Microbiology and Biotechnology, 2025)

The influence of 2,6-Di-tert-butyl-p-cresol stress on the microalga Phaeodactylum tricornutum and phycosphere bacteria community - Xiao Lu; Jie Liu; Xinfeng Xiao; Jianliang Xue; Dongle Cheng; Linlin Zhang (World Journal of Microbiology and Biotechnology, 2025)

The role of immunoglobins in atherosclerosis development; friends or foe? - Linlin Zhang; Peize Li; Yuhui Li; Wantong Qu; Yanyu Shi; Tianyang Zhang; Ying Chen (Molecular and Cellular Biochemistry, 2025)

Are the personality measures for laboratory mice applicable for wild rats? - Jiming Cheng; Huimin He; Linlin Zheng; Hongyu Niu; Hongmao Zhang (Behavioral Ecology and Sociobiology, 2025)

Studying the Impact of the Load Distribution Ratio on the Unsteady Performance of a Dual-Stage Pump-Jet Propulsor - Jiansheng Zhang; Ning Liang; Jianwei Zhang; Linlin Cao; Dazhuan Wu; Wei Zhao; Hanqiao Han (Journal of Marine Science and Engineering, 2025)
This study investigated the impact of different load distribution ratios between two rotors on the unsteady performance of dual-stage pump-jet propulsors using Computational Fluid Dynamics (CFDs) and experimental methods. The Shear Stress Transport (SST) k-ω model was employed to solve turbulence problems, and the numerical simulation method used was validated. The following conclusions were drawn: Different load distribution ratios of the dual-stage rotors have no significant impact on the overall propulsion performance of the propulsor. As the load distribution ratio is aft-shifted, the axial unsteady force of the entire propulsor continuously decreases, with a reduction of up to 53.6%. This is due to the gradual reduction in the energy of the first-stage rotor, leading to a more uniform Blade-Passing Frequency Velocity Harmonic Coefficient (BPFVHC) in front of the second-stage rotor, thereby gradually reducing the unsteady force of the second-stage rotor. The experimental results also indicate that the aft-shifted load model can reduce the sound pressure level of the propulsor. Compared to the prototype propulsor, the sound pressure level at the Blade-Passing Frequency decreases by 6.67 dB, or about 78.5%, in sound energy. This study has important implications for the low-excitation design of dual-stage pump-jet propulsors.

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Pore structure-dependent adsorption of monochloramine by activated carbon - Xin Cheng; Xiaojun Miao; Linlin Li; Xueyan Xue; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2025)

Evaluation of the virulence characteristics of ST11 Salmonella enterica from different sources using a 2D cell model - Linlin Xiao; Yulin Long; Binru Gao; Ying Hu; Tantao Zhang; Qian Xiao; Xiaojie Qin; Xuejuan Xia; Xiang Wang; Zhuosi Li; Qingli Dong (International Journal of Food Microbiology, 2025)

Understanding the effect and mechanism of ε-polylysine on the improvement of tofu storage quality via biofilm inhibition by Bacillus licheniformis and Bacillus amyloliquefaciens - Jingbo Kang; Xin Zhang; Yuyang Huang; Ying Zhu; Linlin Liu; Bingyu Sun; Min Qu; Xiuqing Zhu (Food Bioscience, 2025)

Rational design of micro-cone array on copper host for dendrite-free sodium metal plating - Mengyang Xu; Chengwen Gao; Tsz Wing Tang; Linlin Zhang; Jiawen You; Xing Zhou; Mengjia Xu; Jang-Kyo Kim; Zhengtang Luo (Chemical Engineering Journal, 2025)

Utilizing zeolitic imidazolate framework-8 for enhanced carbon dioxide/methane separation and improved carbon dioxide methanation performance - Weiqi Zhang; Xin Kong; Linlin Bo; Delin Yin; Zhichun Zhang; Xiaojun Fan; Hongping Chen; Jin Yuan (Bioresource Technology, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Magnetic resonance spectroscopy for discriminating primary angiitis of the central nervous system from gliomas and lymphomas - Ping Lu; Lingyun Cui; Lulin Zhang; Huabing wang; Linlin yin; Decai Tian; Xinghu Zhang (Acta Neurologica Belgica, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

Host selection shapes structure and network of microbial community of Epimedium plants along the soil–rhizosphere–plant continuum - Zhaoyu Zhang; Ziying Huang; Xiao Chen; Guozhuang Zhang; Mengzhi Li; Anning Li; Xiaolin Lin; Yuxin Zhou; Yu Zhang; Shilin Chen; Linlin Dong; Guangfei Wei (Rhizosphere, 2025)

GLOSTFM: A global spatiotemporal fusion model integrating multi-source satellite observations to enhance land surface temperature resolution - Qingyan Meng; Shize Chen; Linlin Zhang; Xiaolin Zhu; Yeping Zhang; Peter M. Atkinson (Remote Sensing of Environment, 2025)

Identification and characterization of ClAPRR2, a key candidate gene controlling watermelon stripe color - Shuang Liang; Miaomiao Yang; Linlin Zhang; Xufeng Fang; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Bin Liu; Feishi Luan; Shi Liu (Plant Science, 2025)

Cyclic plasticity of hardened oil well cement paste: A nonlinear kinematic hardening perspective - Linlin Wang; Shuo Chen; Shuitao Zhang; Jiyun Shen; Rongwei Yang (Geomechanics for Energy and the Environment, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

TRIM21 Promotes Endothelial Cell Activation via Accelerating SOCS3 Ubiquitination Degradation in Atherosclerosis - Zhenxuan Hao; Yihuan Wang; Linlin Chen; Yanjun Zhou; Dezhou Fang; Wenxiang Yao; Lili Xiao; Yanzhou Zhang (Cardiovascular Toxicology, 2025)

Research on real-time monitoring and early warning of Tangshan road surface subsidence based on InSAR - Mingzhou Bai; Yanli Qi; Linlin Song; Qihao Wang; Zilun Zhang; Gang Tian (Advances in Space Research, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

A real-time vision guidance method for autonomous longan picking by the UAV - Hengxu Chen; Kaixuan Wu; Hengyi Lin; Haobo Zhou; Zhengqi Zhou; Yuju Mai; Linlin Shi; Meiqi Zhang; Zhe Ma; Peihan Lin; Jun Li (Computers and Electronics in Agriculture, 2025)

Impact of urban land use and anthropogenic heat on winter and summer outdoor thermal comfort in Beijing - Jiangkang Qian; Linlin Zhang; Uwe Schlink; Xinli Hu; Qingyan Meng; Jianfeng Gao (Urban Climate, 2025)

Multi-perspective evaluation framework of three-dimensional cooling and energy saving potential of urban parks based on numerical simulation - Jianfeng Gao; Linlin Zhang; Qingyan Meng; Xinli Hu; Stephen J. Livesley (Sustainable Cities and Society, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

About 868 cal. yr BP tsunami event at the northern South China Sea revealed from offshore sediments - Yuming Wang; Xiaohong Chen; Adam D. Switzer; Linlin Li; Yang Xu; Yukun Wang; Elaine Tan; Peizhen Zhang (Global and Planetary Change, 2025)

Lactic acid bacteria reduce polystyrene micro- and nanoplastics-induced toxicity through their bio-binding capacity and gut environment repair ability - Liuting Shi; Xin Teng; Changyin Wu; Tengxun Zhang; Xing Jin; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Chitong Rao; Gang Wang (Environmental Pollution, 2025)

Improving forest gross primary productivity estimation through climate and trait integration - Hongge Ren; Li Zhang; Min Yan; Bo Zhang; Linlin Ruan (Ecological Modelling, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

Lead-free perovskite Cs3Bi2Br9 quantum dots (QDs)/ultra-thin W18O49 nanobelts S-scheme heterojunction toward optimized photocatalytic CO2 reduction coupled with toluene oxidation - Mai Zhang; Xiangya Zhang; Zhen Zhang; Linlin Zhang; Jianjun Liao; Xiaodong Zhang; Chengjun Ge; Wei Zhou (Chemical Engineering Journal, 2025)

How to optimize urban blue space to maximize its cooling benefits? A case study in megacity of Beijing - Linlin Zhang; Qingyan Meng; Shun Yao; Jiangkang Qian; Jianfeng Gao; Jiahao Wu (Building and Environment, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

RBM15 Knockdown Impairs the Malignancy of Cervical Cancer by Mediating m6A Modification of Decorin - Huimin Wang; Chun Li; Qiong Wei; Enjing Zhang; Yi Yang; Linlin Sha; Dan Wang (Biochemical Genetics, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Corrigendum to “The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments” [166 (2024) 106937] - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

Efficient and low resistance multi-functional UV resistant polyphenylene sulfide non-woven hollow membrane - Mengen Zhang; Qiyang Xi; Linlin Wang; Qinxing Xie; Zhenhuan Li; Maliang Zhang (Journal of Environmental Management, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Bimetallic RuCo anchored CoFe2O4 nanosheets to realize in-depth electronic modulation for boosted structural reconstruction and efficient seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Linlin Dang; Kai Zhang; Qing Guo; Wenhu Li; Taotao Ai; Sumin Wang (Chemical Engineering Journal, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

In situ recurrent Hongshiyan paleolandslides at Ludian, China, and Implications on fault activity and hydro-project risk reduction - Liao Liye; Zeng Qingli; Shi Yongyue; Ma Xuping; Du Linlin; Zhou Jian; Zhang Luqing (Landslides, 2025)

Pharmacokinetics of seven major components in Aβ1-42-treated rats after oral administration of an aqueous extract of Curculiginis Rhizoma and Epimedii Folium - Junzuo Zheng; Jun Wang; Linlin Chen; Xuelian Jiang; Xuesong Zhang; Wenqi Ai; Yuman Xie; Ping Wang; Zhou Lan; Xiaoping Ding (Journal of Natural Medicines, 2025)

Distribution of microplastics in the soils of a petrochemical industrial region in China: Ecological and Human Health Risks - Yuting Guo; Rongshan Wu; Heng Zhang; Changsheng Guo; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2025)

Comprehensive host cell proteins profiling in biopharmaceuticals by a sensitivity enhanced mass spectrometry strategy using TMT-labeling and signal boosting - Andong Xue; Linlin Kong; Jialin Li; Yuxin Jiao; Zhishang Hu; Bin Fu; Guibin Wang; Wanjun Zhang; Jianheng Li; Weijie Qin (Analytica Chimica Acta, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Copper Intake and Mortality Among Asthmatic Adults: A Cohort Study - Linlin Huang; Hegan Zhang; Rongjuan Zhuang; Jun Wen (Biological Trace Element Research, 2024)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Feasibility evaluation of cottonseed protein concentrate to replace soybean meal in the diet of juvenile grass carp (Ctenopharyngodon idellus): Growth performance, antioxidant capacity, intestinal health and microflora composition - Linlin Yang; Minglang Cai; Lei Zhong; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

The complete genome sequence of Streptomyces sp. FIM 95-F1, a marine actinomycete that produces the antifungal antibiotic scopafungin - Peng Fei; Lin Yangjun; Zhuang Yuee; Lin Ping; Liu Chengzhi; Chen Linlin; Jiang Hong; Lian Yunyang; Zhang Wenzhou; Huang Youxia (Marine Genomics, 2024)

High mechanical property, hydrophobic and fire-retardant cellulose film derived from kenaf degumming wastewater - Shixing Wang; Xiaolong Qiao; Linlin Li; Hailong Lu; Yuanming Zhang; Guangting Han; Haoxi Ben; Wei Jiang (Journal of Environmental Chemical Engineering, 2024)

Simulation of diffusion of combustible refrigerants R1234yf and R290 leakage in automotive air conditioning - Linlin Wang; Yu He; Jiabao Ren; Dan Wang; Baomin Dai; Zhe Zhang (International Journal of Refrigeration, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

Umbrella effect of spotted seal conservation and achieving 30 × 30 targets in the Yellow Sea ecoregion - Hongfei Zhuang; Fangyuan Qu; Zhichuang Lu; Linlin Zhao; Zhaohui Zhang (Reviews in Fish Biology and Fisheries, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Evaluation of soybean meal replacement by Clostridium autoethanogenum protein in diets for juvenile grass carp (Ctenopharyngodon idellus) - Linlin Yang; Minglang Cai; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

Evaluation of Tembusu virus single-round infectious particle as vaccine vector in chickens - Yunzhen Huang; Zhe Liu; Junqin Zhang; Jiawen Dong; Linlin Li; Yong Xiang; Ruihuan Kuang; Shimin Gao; Minhua Sun; Yongjie Liu (Veterinary Microbiology, 2024)

Unraveling the effect of electricity price on electric vehicle charging behavior: A case study in Shenzhen, China - Haoxuan Kuang; Xinyu Zhang; Haohao Qu; Linlin You; Rui Zhu; Jun Li (Sustainable Cities and Society, 2024)

Estimating global 0.1° scale gridded anthropogenic CO2 emissions using TROPOMI NO2 and a data-driven method - Yucong Zhang; Shanshan Du; Linlin Guan; Xiaoyu Chen; Liping Lei; Liangyun Liu (Science of The Total Environment, 2024)

The role of trade policy uncertainty on contemporaneous and lagged connectedness between critical raw materials and high-tech markets: Evidence from China - Wang Gao; Linlin Zhang; Haizhen Zhang; Hongwei Zhang (Resources Policy, 2024)

A novel flow control method suppressing tip leakage vortex of a hydrofoil applied for ducted devices - Fadong Gu; Lei Shi; Xi Shen; Guangjian Zhang; Linlin Geng; Desheng Zhang; B.P.M. (Bart) van Esch (Ocean Engineering, 2024)

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Decreased formulation pH and protein preheating treatment enhance the interaction, storage stability, and bioaccessibility of caseinate-bound lutein/zeaxanthin - Gang Zhang; Linlin He; Xin Qi; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhuang Ding; Zhengping Wang; Sangeeta Prakash (Food Research International, 2024)

The casein in sheep milk processed by cold plasma technology: Phosphorylation degree, functional properties, oxidation characteristics, and structure - Jiaying Zhang; Jiaqing Song; Shuangshuang Wang; Yangyu Su; Linlin Wang; Wupeng Ge (Food Chemistry, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

Quantifying the changes in solute transport caused by human influence on river connectivity in inland river basins - Wenhao Zhang; Guofeng Zhu; Ling Zhao; Lei Wang; Dongdong Qiu; Linlin Ye; Siyu Lu; Xinrui Lin (CATENA, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

Transcriptomic analysis uncovers a biphasic response to precocious Eimeria acervulina infection in chicken duodenal tissue - Ning Zhang; Jie Liu; Yuanyuan Zhang; Linlin Chen; Sixin Zhang; Xianyong Liu; Xinming Tang; Xiaolong Gu; Shiyi Chen; Xun Suo (Veterinary Parasitology, 2024)

Biomass-derived carbon dots with pharmacological activity for biomedicine: Recent advances and future perspectives - Yue Liu; Linlin Zhang; Huijuan Cai; Xiaoli Qu; Junbiao Chang; Geoffrey I.N. Waterhouse; Siyu Lu (Science Bulletin, 2024)

Iron-nitrogen coupling mediates soil microbial community composition and gene expression during the formation of rusty root in Panax ginseng from three northeast provinces in China - Qiao Jin; Linlin Zhang; Keming Cao; Xiaoxi Pan; Zhengbo Liu; Yiming Guan; Xiangxi Zuo; Yayu Zhang; Qiuxia Wang (Journal of Environmental Chemical Engineering, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Finer topographic data improves distribution modeling of Picea crassifolia in the northern Qilian Mountains - Xiang Zhang; Linlin Gao; Yu Luo; Yiyun Yuan; Baolong Ma; Yang Deng (Journal of Mountain Science, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

Study on China’s Farmland–Grain resource curse: Empirical testing based on 31 Provinces and 2843 Counties - Renyi Yang; Changbiao Zhong; Zisheng Yang; Shiqin Yang; Guanqiu Ji; Jingke Yu; Linlin Cao; Jinrong Yang; Lei Luo; Yicong Shen; Yongdong Zhang (Land Use Policy, 2024)

Daily trunk radial growth patterns in relation to precipitation in orange trees in the dry-hot valley region of Southwest China - Xuehui Wei; Dianyu Chen; Panpan Hou; Xiaotao Hu; Lucheng Qiu; Jingying Zhang; Xingwu Duan; Linlin Zhang; Jing Guo (Journal of Hydrology, 2024)

Water-dependent effects of biodegradable microplastics on arsenic fractionation in soil: Insights from enzyme degradation and synchrotron-based X-ray analysis - Kailin Gong; Tianzi Liu; Cheng Peng; Ziyi Zhao; Xiang Xu; Xuechun Shao; Xuan Zhao; Linlin Qiu; Wenwen Xie; Qian Sui; Wei Zhang (Journal of Hazardous Materials, 2024)

Transformation and environmental risk of 90Sr and 137Cs under extreme rainstorm at a proposed nuclear facility site in China - Jun Zhu; Ying Hao; Chao Chen; Ting Wang; Ke Chen; Linlin Zhang; Aiming Zhang; Tian Xie; Qiulan Zhang (Journal of Environmental Radioactivity, 2024)

Fabrication of polysaccharide-coated oleanolic acid-curcumin-coassembled nanoparticles (OA/Cur NPs): Enhancement of colloidal stability and water solubility - Linlin Yan; Han Liu; Yuhui Wang; Lulu Zhang; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2024)

Spatial diffusion of potentially toxic elements in soils around non-ferrous metal mines - Linlin Li; Yunlong Zhang; Lingyan Zhang; Bo Wu; Xinhong Gan (Environmental Research, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

High-amylose starch-based gel as green adhesive for plywood: Adhesive property, water-resistance, and flame-retardancy - Yaoxing Chen; Yongjing Rao; Peng Liu; Linlin Wu; Guojie Zhang; Jianguo Zhang; Fengwei Xie (Carbohydrate Polymers, 2024)

Monitoring slope stabilization of a reactivated landslide in the Three Gorges Reservoir Region (China) with multi-source satellite SAR and optical datasets - Jianming Kuang; Linlin Ge; Alex Hay-Man Ng; Stuart R. Clark; Sadra Karimzadeh; Masashi Matsuoka; Zheyuan Du; Qi Zhang (Landslides, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

Intermittent irrigation as a solution for reduced emissions and increased yields in ratoon rice systems - Lang Zhang; Linlin Li; Qiyuan Tang; Huaqin Xu; Huabin Zheng; Faming Wang; Jianwu Tang (Plant and Soil, 2024)

Differences and implications of strontium distribution coefficient on various granite compositional materials - Fangfei Cai; Xiaoying Zhang; Funing Ma; Linlin Qi; Di Lu; Zhenxue Dai (Environmental Science and Pollution Research, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Integrative proteomic-metabolomics strategy reveals the regulators and mechanism of enhancing cyclic lipopeptides in the high-cell-density fermentation of Bacillus subtilis S1702 - Bo Zhang; Linlin Xu; Hui Yang; Zhengjun Pang; Wenshuo Zhang; Fenghuan Wang; Huilin Liu; Junfeng Fan; Bolin Zhang (Process Safety and Environmental Protection, 2024)

Extraction of organic solvents and preferential recovery of lithium from spent lithium-ion batteries by in-situ carbothermal reduction - Jian Zou; Ruihan Zhang; Yali Zhang; Linlin Chen; Yaoguo Huang; Xianfu Sun (Process Safety and Environmental Protection, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

Coupling sedimentary records of anthropogenic metal(loid)s in urban waterscape parks with the “Coal to Gas” transition - Shen Yu; Tao Ma; Linlin Zhang; Qi Li; Min Zhou (Journal of Hazardous Materials, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

A critical review of characteristics of domestic wastewater and key treatment techniques in Chinese villages - Jing Zhang; Yungeng Jiang; Heyu Zhang; Dan Feng; Hongling Bu; Linlin Li; Shaoyong Lu (Science of The Total Environment, 2024)

Wen-Yi and Chinese medicine: Why we need to pay attention? - Yibai Xiong; Linlin Bao; Yan Ma; Ling Zhang; Chuan Qin; Luqi Huang (Science Bulletin, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Polycyclic aromatic hydrocarbons exposure and arterial stiffness-related plasma miRNAs: A panel study - Ziqian Zhang; Conghua Bai; Lei Zhao; Linlin Liu; Wenting Guo; Miao Liu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Toxicology and Pharmacology, 2024)

Seasonal aridity regulates drivers and temporal variability of wood phenology: A meta-analysis of dendrometer monitoring data across the Northern Hemisphere - Yuhang Zhang; Linlin Gao; Yang Deng; Qianling Huang; Yiyun Yuan; Xingying Shi; Xiaohua Gou (Dendrochronologia, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

An end-capping strategy for shape memory phthalonitrile resins via annealing enables conductivity and wave-absorption - Rongxiang Hu; Fenghua Zhang; Lan Luo; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2024)

A tree-ring based streamflow reconstruction for the Taohe River (Gannan Plateau, China) associated with the Asian-Pacific Oscillation since 1325 CE - Xingying Shi; Linlin Gao; Yang Deng; Yuhang Zhang; Xiang Zhang; Xiaohua Gou (CATENA, 2024)

Island-based GNSS-IR network for tsunami detecting and warning - Linlin Li; Qiang Qiu; Mai Ye; Dongju Peng; Ya-Ju Hsu; Peitao Wang; Huabin Shi; Kristine M. Larson; Peizhen Zhang (Coastal Engineering, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Measurement of Elastic Bi-modulus of Rock-type Materials: Insight from comparative and parallel tests - Yan Zhang; Hao Zheng; Huiling He; Peng Sha; Linlin Wang; Shengwen Qi; Xiaolin Huang; Jianhong Ye (Bulletin of Engineering Geology and the Environment, 2024)

The Observed Near-Surface Energy Exchange Processes over Arctic Glacier in Summer - Libo Zhou; Jinhuan Zhu; Linlin Kong; Peng Li; Shupo Ma; Fei Li; Han Zou; Meigen Zhang; Irina Repina (Journal of Meteorological Research, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Editorial: The response, adaptation, and evolution of marine molluscs - Xiao Liang; Linlin Zhang; Yingxiang Li (Frontiers in Marine Science, 2024)

EB-Net: an efficient balanced network for accuracy and speed of remote sensing detection - Dehua Zhang; Dechen Wang; Changcheng Yu; Xinyuan Hao; Linlin Liang (International Journal of Remote Sensing, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Towards robust classification of multi-view remote sensing images with partial data availability - Maofan Zhao; Qingyan Meng; Lifeng Wang; Linlin Zhang; Xinli Hu; Wenxu Shi (Remote Sensing of Environment, 2024)

Control of postharvest soft rot of green peppers by Bacillus subtilis through regulating ROS metabolism - Peipei Feng; Xiaoyun Zhang; Esa Abiso Godana; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Linlin Gao; Jun Li; Lina Zhao; Hongyin Zhang (Physiological and Molecular Plant Pathology, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Adsorption-desorption of 241Am(Ⅲ) on montmorillonite colloids and quartz sand: Effects of pH, ionic strength, colloid concentration and grain size - Linlin Zhang; Ling Li; Ke Chen; Qiulan Zhang; Jingli Shao; Yali Cui; Jun Zhu; Aiming Zhang; Song Yang (Journal of Environmental Radioactivity, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

High spatial and temporal resolution multi-source anthropogenic heat estimation for China - Jiangkang Qian; Linlin Zhang; Uwe Schlink; Qingyan Meng; Xue Liu; Tamás Janscó (Resources, Conservation and Recycling, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

CO2 methanation reaction over La-modified NiAl catalysts derived from hydrotalcite-like precursors - Linlin Zhou; Xiaoming Guo; Xu Hu; Yaxin Zhang; Jinglin Cheng; Qiangsheng Guo (Fuel, 2024)

Proteomic insights into the response of Halomonas sp. MNB13 to excess Mn(Ⅱ) and the role of H2S in Mn(Ⅱ) resistance - Xiuli Xu; Fuhang Song; Guoliang Zhang; Linlin Ma; Na Yang (Environmental Research, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Mild low-temperature photothermal therapy demonstrated a distinctive 'hot spring' effect in the multichannel regulation of atherosclerosis instead of inducing foam cell apoptosis - Jie Sheng; Ziyue Zu; Jianchen Qi; Yugang Zhang; Haoguang Wu; Zhicheng Wang; Yu Miao; Tao Zheng; Sheng Wang; Linlin Zhang; Guangming Lu; Longjiang Zhang (Chemical Engineering Journal, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Clinical Application of Polygenic Risk Score in IgA Nephropathy - Linlin Xu; Ting Gan; Pei Chen; Yang Liu; Shu Qu; Sufang Shi; Lijun Liu; Xujie Zhou; Jicheng Lv; Hong Zhang (Phenomics, 2024)

Clinical epidemiology of adenovirus pneumonia among Chinese hospitalized children - Jiao Tian; Xinyu Wang; Qi Li; Linlin Zhang; Junhong Ai; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Archives of Microbiology, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Revealing the degrading-possibility of methyl red by two azoreductases of Anoxybacillus sp. PDR2 based on molecular docking - Shulin Zhang; Linlin Feng; Yanyan Han; Zihang Xu; Luhui Xu; Xuejiao An; Qinghua Zhang (Chemosphere, 2024)

Coupled cooling effects between urban parks and surrounding building morphologies based on the microclimate evaluation framework integrating remote sensing data - Qingyan Meng; Jianfeng Gao; Linlin Zhang; Xinli Hu; Jiangkang Qian; Tamás Jancsó (Sustainable Cities and Society, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Cyanide removal of gold cyanide residues by manganese compounds as new decyanation reagents - Wenwen Han; Hongying Yang; Linlin Tong; Qin Zhang; Zhenan Jin (Science of The Total Environment, 2024)

Subsurface eddies east of the Philippines: Geographic characteristics, vertical structures, volume and thermohaline transport - Linlin Zhang; Weiqi Song; Yuchao Hui; Zhenxiao Wang; Dunxin Hu (Progress in Oceanography, 2024)

Applying bio-oxidation waste solution into two-stage oxidation process to enhance the bio-oxidation of pyrite: Insight on enhanced mechanism - Shiqi Zhang; Hongying Yang; Linlin Tong; Pengcheng Ma; Zuochun Luan; Qifei Sun (Journal of Water Process Engineering, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Influence of polysaccharide-based co-encapsulants on efficiency, stability, and release of vitamins B12 and D3 in multilayered microcapsules - Linlin He; Shihong Hu; Gang Zhang; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhengping Wang; Prakash Sangeeta; Zhuang Ding (Journal of Food Engineering, 2024)

Preparation and characterization of zein-tannic acid nanoparticles/chitosan composite films and application in the preservation of sugar oranges - Shuangjian Li; Xiaoli Liu; Xiaoqian Zhang; Linlin Fan; Fan Wang; Jianzhong Zhou; Hongzhi Zhang (Food Chemistry, 2024)

Piezoelectric effect-assisted Z-scheme heterojunction ZnIn2S4/BaTiO3 for improved photocatalytic reduction of CO2 to CO - Shanyue Lu; Shengwei Zhang; Linlin Li; Cong Liu; Zhou Li; Dan Luo (Chemical Engineering Journal, 2024)

Photocatalytic chitosan-based bactericidal films incorporated with WO3/AgBr/Ag and activated carbon for ethylene removal and application to banana preservation - Feng Xiao; Yewen Xiao; Wei Ji; Linlin Li; Yimeng Zhang; Minmin Chen; Hualin Wang (Carbohydrate Polymers, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

N-methyl pyrrolidone manufacturing wastewater as the electron donor for denitrification: From bench to pilot scale - Songyun Chen; Xiaohui Zhu; Ge Zhu; Bin Liang; Jin Luo; Danyang Zhu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Science of The Total Environment, 2024)

Microplastics alter Cr accumulation and fruit quality in Cr(VI) contaminated soil-cucumber system during the lifecycle: Insight from rhizosphere bacteria and root metabolism - Kailin Gong; Qi Zhang; Xuechun Shao; Yonghong Wu; Zhihua Qiao; Linlin Qiu; Wei Zhang; Cheng Peng (Science of The Total Environment, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

The pollution of airborne ARGs and microorganisms during wastewater treatment process and their UV mediated removal mechanism - Yanjie Wang; Hao Chen; Liying Yang; Song Zhang; Kai Yang; Linlin Hua (Journal of Water Process Engineering, 2024)

Electrocatalytic degradation of nitrogenous heterocycles on confined particle electrodes derived from ZIF-67 - Yu Liu; Linlin Qin; Yiming Qin; Tong Yang; Haoran Lu; Yulong Liu; Qiqi Zhang; Wenyan Liang (Journal of Hazardous Materials, 2024)

Investigating the role of Na-bentonite colloids in facilitating Sr transport in granite minerals through column experiments and modeling - Xiaoying Zhang; Fangfei Cai; Funing Ma; Paul Reimus; Linlin Qi; Di Lu; Mohamad Reza Soltanian; Zhenxue Dai (Journal of Hazardous Materials, 2024)

An urban metabolism framework purpose to assess the dynamics of linear alkylbenzenes (LABs) discharge flows and driving forces at the city level in Guangdong province, China - Zihao Wu; Linlin Xia; Junye Zhong; Yan Zhang (Environmental Pollution, 2024)

Cu-hierarchical porous carbon anodes derived from metal-organic frameworks for long-lasting and high-energy lithium storage - Bing Zhu; Manshu Zhang; Yangai Liu; Yicen Liu; Xi Zhang; Yahui Song; Linlin Wang; Ruiyu Mi (Chemical Engineering Journal, 2024)

Structure-defined viologen-polyoxometalate modified separator dominating endurable Li-S batteries by a synergistic adsorption-electrocatalysis mechanism - Yuxi Zhang; Yundong Cao; Linlin Fan; Guilin Shi; Tianyu Zheng; Hong Liu; Jian Song; Guanggang Gao (Chemical Engineering Journal, 2024)

Bifidobacteria in disease: from head to toe - Weiliang Zhang; Qiang Jia; Mingming Han; Xin Zhang; Limin Guo; Shichao Sun; Wenhui Yin; Cunxiang Bo; Ru Han; Linlin Sai (Folia Microbiologica, 2024)

Vertical distribution of intraseasonal variation signals in the Kuroshio Current source area during 2018–2020 - Haobo Gong; Fujun Wang; Feng Liu; Linlin Zhang; Dunxin Hu (Frontiers in Marine Science, 2024)
In the Kuroshio Current (KC) source area, intraseasonal variation (ISV) plays a significant role in dynamic oceanic processes. This study used data collected from three moorings (122.7°E, 123°E, 123.3°E) along 18°N from January 2018 to May 2020 to investigate the ISVs of meridional velocities. Notably, our findings reveal that the ISV above 200 m has a period of approximately 56 days and its intensity exhibits a gradual increase toward the west. For the 500–800 m depth interval, the ISV period is 73 days at 122.7°E/18°N and 60 days at 123.3°E/18°N. This discrepancy indicates that the ISVs have different vertical structures and frequencies at 122.7°E and 123.3°E along 18°N. In particular, at 122.7°E/18°N, the distinctiveness of two different periods of ISVs in surface and subsurface layers was more pronounced in 2018 than in 2019. The analyses of eddy kinetic energy distribution and eddy tracking indicate a connection between ISV in stratification and locally generated mesoscale eddies in the KC source area. Specifically, the stronger eddy activity in 2018, in contrast with that in 2019, correlates with a more pronounced ISV. Energy analysis demonstrates a distinct positivity in the baroclinic conversion rate (BC) in the surface layer (upper 200 m) of the KC source region, surpassing the absolute value of the barotropic conversion rate (BT). This finding indicates a notable shift of energy from eddy available potential energy to eddy kinetic energy, strengthening the high-frequency ISV signals in this area. In the subsurface layer, a strong negative BT is observed west of 122.8°E, with its absolute value exceeding the BC. This finding indicates that the energy is converted from eddy kinetic energy into mean kinetic energy, resulting in the appearance of the Luzon Undercurrent (LUC) at mooring station 122.7°E/18°N, characterized by a low frequency of ISV. Contrastingly, a positive BT plays a dominant role at 123.3°E/18°N, leading to the disappearance of the LUC amid an apparent presence of high-frequency ISV.

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Seismic behavior of embedded rubberized concrete-filled corrugated steel tube column-to-foundation connections: Experimental, numerical modelling, and design - Mingyang Feng; Baodong Liu; Linlin Zhang; Yaoyao Wang; Haibo Sun (Soil Dynamics and Earthquake Engineering, 2024)

GhFB15 is an F-box protein that modulates the response to salinity by regulating flavonoid biosynthesis - Zhao Geng; Haikuan Dou; Jianguang Liu; Guiyuan Zhao; Zetong An; Linlin Liu; Ning Zhao; Hanshuang Zhang; Yongqiang Wang (Plant Science, 2024)

Dynamic behaviors of cavitation bubbles near biomimetic surfaces: A numerical study - Hongbo Shi; Hang Zhang; Linlin Geng; Sen Qu; Xikun Wang; Petr A. Nikrityuk (Ocean Engineering, 2024)

How the subsurface wastewater infiltration systems with iron‑carbon micro-electrolytic substrate achieve high pollutants removal: A metabolomic view - Yinghua Li; Linlin Peng; Yiyan Wang; Yue Zhang; Fei Su; Jie Qian (Journal of Water Process Engineering, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Influence of sampling location and processing on the assembly and network of Polygoni Multiflori Radix surface microbiome - Guangfei Wei; Yichuan Liang; Guozhuang Zhang; Zhaoyu Zhang; Yongqing Zhang; Shilin Chen; Linlin Dong (International Journal of Food Microbiology, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

Performance and mechanism of Al, N co-doped carbon/nano-TiO2 photocatalytic oxidation for the removal of ammonia nitrogen and Ni/Co complexes from ternary precursor wastewater - Peize Li; Yaoguo Huang; Yali Zhang; Linlin Chen (Chemical Engineering Journal, 2024)

Fabrication and mechanism of La/Al bimetallic organic frameworks for phosphate removal - Zheng Zhu; Linlin Qin; Yulong Liu; Qiqi Zhang; Peng Cheng; Wenyan Liang (Chemical Engineering Journal, 2024)

One-step, reagent-free construction of nano-enzyme as visual and reusable biosensor for oxidase substrates - Ke Quan; Yuqing Zeng; Wenke Zhang; Fengfeng Li; Mengjiao Li; Zhihe Qing; Linlin Wu (Analytica Chimica Acta, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

S doped g-C3N5 for highly efficient photocatalytic H2O2 production and PPCPs degradation via directional transfer of electrons - Wenjuan Wang; Nan Zhou; Yakun Li; Zhengqiaoruo Zhu; Xiguo Chen; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

Advancing ocean subsurface thermal structure estimation in the Pacific Ocean: A multi-model ensemble machine learning approach - Jifeng Qi; Linlin Zhang; Baoshu Yin; Delei Li; Bowen Xie; Guimin Sun (Dynamics of Atmospheres and Oceans, 2023)

A novel lateral epitaxial Bi2O3@BiOCl heterostructure for photocatalytic antibiotic degradation in an internal circulation fluidized bed reactor - Yilin Dong; Shaoxuan Pang; Fuqiang Zhang; Dongyu Xu; Qiuwen Wang; Kang Wang; Lijun Zhang; Linlin Liang; Zhijun Ren; Pengfei Wang (Chemical Engineering Journal, 2023)

Multidimensional cross-linked network strategies for Rapidly, Reconfigurable, refoldable shape memory polymer - Lan Luo; Fenghua Zhang; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Rhizosphere effects on the microbial community: Specificity and conservatism across geographically disjunct Panax species - Guozhuang Zhang; Liping Shi; Congsheng Liu; Zhixin Huang; Yuqing Zheng; Linlin Dong (Applied Soil Ecology, 2023)

Establishment of ultrasensitive immunoassay strip based on colloidal gold-McAb probe for detecting cyproheptadine hydrochloride and six phenothiazines in feed - Xiaofei Hu; Guanqiong Na; Yaning Sun; Yunrui Xing; Linlin Chen; Zhang Gaiping (Food Additives & Contaminants: Part A, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Investigating the influence of bentonite colloids on strontium sorption in granite under various hydrogeochemical conditions - Fangfei Cai; Funing Ma; Xiaoying Zhang; Paul Reimus; Linlin Qi; Yu Wang; Di Lu; Hung Vo Thanh; Zhenxue Dai (Science of The Total Environment, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

Continuous flow fluorination facilitated by KF assisted by water: From batch to continuous flow - Tao Shen; Chenjun Jiang; Yifeng Lai; Linlin Wu; Liangquan Zhang; Chao Qian (Journal of Fluorine Chemistry, 2023)

Structural and gelling properties of whey proteins influenced by various acids: Experimental and computational approaches - Linlin Zhang; Zhuo Zhang; Stephen R. Euston; Bo Li; Erhu Li; Caixia Fu; Guodong Chen (Food Hydrocolloids, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

A two-centennial perspective on spatially compounding hydroclimate events in arid and semi-arid north China - Qian Li; Linlin Gao; Yang Deng; Xiang Zhang; Yongkang Duan; Xiaohua Gou (Quaternary Science Reviews, 2023)

A novel ZnFe2O4 intermediate layer for improving the electrocatalytic performance of Ti/Ce-PbO2 anode toward Levofloxacin removal - Linlin Dong; Zhong Zhuang; Guohua Dong; Hao Zhang; Min Zhu; Zhuanfang Zhang; Ming Zhao; Jinlong Li; Wenzhi Zhang (Journal of Environmental Chemical Engineering, 2023)

Phosphorus and sulfur regulation of ferrum doped carbon nitride for efficient photocatalytic PPCPs degradation under visible-light irradiation - Zhengqiaoruo Zhu; Nan Zhou; Yakun Li; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

The effects of selenium on the growth and bone development in the weaned rats - Hongan Li; Linlin Jia; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Bioscience, 2023)

Construction of CoTiO3/TiO2/Ti composite catalytic membrane for degradation of tetracycline via peroxymonosulfate activation: Reactive oxygen species and electron transfer pathways - Yi Li; Linlin Wang; Longfei Wang; Weijie Wu; Fangjie Zhang; Haijiao Xie (Chemical Engineering Journal, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Application of carbon dots in food preservation: a critical review for packaging enhancers and food preservatives - Linlin Zhao; Min Zhang; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

A uniform methodology of local cooling and warming effects for different urban site types: multi-perspective assessment based on four northern Chinese cities - Jianfeng Gao; Qingyan Meng; Die Hu; Linlin Zhang; Xinli Hu; Jiangkang Qian (Sustainable Cities and Society, 2023)

Assessment on the stereoselective behavior of cyflumetofen to earthworms (Eisenia foetida): Degradation, bioaccumulation, toxicity mechanism, and metabolites - Linlin Shi; Chao Shen; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Science of The Total Environment, 2023)

Quadristerols A−G: Seven undescribed ergosterols from Aspergillus quadrilineata - Mengsha Wei; Xiaoxin Li; Hong Liao; Linlin Liu; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2023)

Occurrence of fungi and mycotoxins in herbal medicines and rapid detection of toxin-producing fungi - Guangfei Wei; Xiaotong Guo; Yichuan Liang; Congsheng Liu; Guozhuang Zhang; Conglian Liang; Zhixin Huang; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Pollution, 2023)

Geranylgeranylacetone, an inducer of heat shock protein 70, attenuates pulmonary fibrosis via inhibiting NF-κB/NOX4/ROS signalling pathway in vitro and in vivo - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Chemico-Biological Interactions, 2023)

GGA (geranylgeranylacetone) ameliorates bleomycin-induced lung inflammation and pulmonary fibrosis by inhibiting apoptosis and oxidative stress - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Molecular Biology Reports, 2023)

Schemes for enhanced antioxidant stability in frying meat: a review of frying process using single oil and blended oils - Ju Shen; Min Zhang; Linlin Zhao; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Characteristics of anthropogenic heat with different modeling ideas and its driving effect on urban heat islands in seven typical Chinese cities - Jiangkang Qian; Qingyan Meng; Linlin Zhang; Uwe Schlink; Xinli Hu; Jianfeng Gao (Science of The Total Environment, 2023)

Anthropogenic heat variation during the COVID-19 pandemic control measures in four Chinese megacities - Qingyan Meng; Jiangkang Qian; Uwe Schlink; Linlin Zhang; Xinli Hu; Jianfeng Gao; Qiao Wang (Remote Sensing of Environment, 2023)

Paleoproterozoic skarn mineralization events and geodynamic background in the Jiao-Liao-Ji Belt: Geological, geochemical and chronological evidence from the Daqinggou Fe–Cu polymetallic deposit in Ji'an, NE China - YanPeng Liu; JingGui Sun; LinLin Wang; ZhiKai Xu; ChengLin Bai; Xiang Chang; TingTing Zhang (Precambrian Research, 2023)

Insights into gas flow behavior in venturi aerator by CFD-PBM model and verification of its efficiency in sludge reduction through O3 aeration - Hongli Li; Qilei Zhang; Ming Zeng; Jingguo Cao; Qingyu Zhao; Linlin Hao (Journal of Water Process Engineering, 2023)

Dualistic cascade convolutional neural network dedicated to fully PolSAR image ship detection - Gui Gao; Qilin Bai; Chuan Zhang; Linlin Zhang; Libo Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Urinary phthalate metabolites and heart rate variability: A panel study - Ziqian Zhang; Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Jie Yu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Pollution, 2023)

A parallel Python-based tool for meshing watershed rivers at continental scale - Fei Ye; Linlin Cui; Yinglong Zhang; Zhengui Wang; Saeed Moghimi; Edward Myers; Greg Seroka; Alan Zundel; Soroosh Mani; John G.W. Kelley (Environmental Modelling & Software, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

MiR-590-5p promotes cisplatin resistance via targeting hMSH2 in ovarian cancer - Bing Li; Xuejie Xu; Linlin Zheng; Xiaojie Jiang; Jing Lin; Guoliang Zhang (Molecular Biology Reports, 2023)

Recognize enhanced temporal-spatial-spectral features with a parallel multi-branch CNN and GRU - Linlin Wang; Mingai Li; Liyuan Zhang (Medical & Biological Engineering & Computing, 2023)

Prognostic value of the WT-1 gene combined with recurrent cytogenetic genes in acute myeloid leukemia - Qing Zhang; Linlin Liu; Haotian Yan; Xiyang Ren; Mei Zhou; Shudao Xiong; Huiping Wang; Qianshan Tao; Zhimin Zhai (Immunogenetics, 2023)

Biochar accelerates the start-up of the anammox process: Phenomenon and potential mechanisms - Hui Chen; Shenbo Cao; Linlin Chen; Zhicheng Zhang; Juesheng Tian; Rencun Jin; Jun Yao (Journal of Water Process Engineering, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Spatial response relationship between mining and industrial activities and eco-environmental risks in mineral resource–based areas - Yang Li; Lingyan Zhang; Bo Wu; Linlin Li; Yunlong Zhang (Environmental Science and Pollution Research, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Systematic assessment of cyflumetofen toxicity in soil-earthworm (Eisenia fetida) microcosms - Linlin Shi; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Journal of Hazardous Materials, 2023)

In vitro gastrointestinal digestion of whole grain noodles supplemented with soluble dietary fiber and their effects on children fecal microbiota - Linlin Gao; Lin Zhang; Huan Liu; Jielun Hu (Food Bioscience, 2023)

Glyphosate induces autophagy in hepatic L8824 cell line through NO-mediated activation of RAS/RAF/MEK/ERK signaling pathway and energy metabolism disorders - Linlin Zhang; Lu Chen; Meng Qi; Fuchang Yu; Xiaotong Ni; Haozheng Hong; Haotian Xu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Experimental investigation on seismic performance of self-centering frictional cast-in-situ beam-column joints - Xiao Lu; Hang Xu; Xuemin Zhang; Linlin Xie (Engineering Structures, 2023)

Elevation-dependent tree growth response to recent warming and drought on eastern Tibetan Plateau - Dingcai Yin; Xiaohua Gou; Haijiang Yang; Kai Wang; Jie Liu; Yiran Zhang; Linlin Gao (Climatic Change, 2023)

Upscaling dispersivity for conservative solute transport in naturally fractured media - Sida Jia; Zhenxue Dai; Zhichao Zhou; Hui Ling; Zhijie Yang; Linlin Qi; Zihao Wang; Xiaoying Zhang; Hung Vo Thanh; Mohamad Reza Soltanian (Water Research, 2023)

Role of local climate zones and urban ventilation in canopy urban heat island–heatwave interaction in Nanjing megacity, China - Weishou Tian; Yuanjian Yang; Linlin Wang; Lian Zong; Yanhao Zhang; Duanyang Liu (Urban Climate, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Effect of bubbles on the gas–water migration during gas hydrate dissociation by depressurization - Shicai Sun; Zhendong Yang; Linlin Gu; Haifei Lin; Changxing Zhang (Fuel, 2023)

Allosteric synthetic antibody (Allo-SyAb) for improved cancer immunotherapy - Jiajing Chen; Mengchen Xu; Yongxin Zhang; Linlin Xu; Shuyue Zhao; Yingli An; Rujiang Ma; Yang Liu; Feihe Ma; Linqi Shi (Chemical Engineering Journal, 2023)

Unevenly spatiotemporal distribution of urban excess warming in coastal Shanghai megacity, China: Roles of geophysical environment, ventilation and sea breezes - Yuanjian Yang; Min Guo; Linlin Wang; Lian Zong; Duanyang Liu; Wenjie Zhang; Mengya Wang; Bingcheng Wan; Yide Guo (Building and Environment, 2023)

Influence of monsoon anomalies on intra-annual density fluctuations of Chinese pine in the Loess Plateau - Shuangjuan Wang; Yang Deng; Linlin Gao; Yuhang Zhang; Xingying Shi; Xiaohua Gou (International Journal of Biometeorology, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms - Weiqin Xing; Hongpei Geng; Yali Wang; Linlin Zhao; Yongqiang Yang; Yale Wang; Shuhang Tian; Yongxin Cao; Zhe Zhang; Liping Li (Chemosphere, 2023)

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Global analysis of gene expression profiles and gout symptoms in goslings infected with goose astrovirus - Chenggang Liu; Linlin Li; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Yong Xiang; Jin Jin; Xianshe Huang; Gang Wang; Minhua Sun; Ming Liao (Veterinary Microbiology, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Bimetal Cu and Fe modified g-C3N4 sheets grown on carbon skeleton for efficient and selective photocatalytic reduction of CO2 to CO - Songyuan Bian; Xueyan Li; Long Zhang; Libin Wang; Jingzhen Wang; Qing Xu; Linlin Zang; Yanhong Zhang; Liguo Sun (Journal of Environmental Chemical Engineering, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Interactions between zein and anthocyanins at different pH: Structural characterization, binding mechanism and stability - Shuangjian Li; Xiang Wang; Xiaoqian Zhang; Hui Zhang; Siyuan Li; Jianzhong Zhou; Linlin Fan (Food Research International, 2023)

The structural characterization of polysaccharides from three cultivars of Moringa oleifera Lam. root and their effects on human intestinal microflora - Linlin Jia; Xiaoqiang Peng; Zeyuan Deng; Bing Zhang; Hongyan Li (Food Bioscience, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

Tannin alleviates glyphosate exposure-induced apoptosis, necrosis and immune dysfunction in hepatic L8824 cell line by inhibiting ROS/PTEN/PI3K/AKT pathway - Linlin Zhang; Lu Chen; Dayong Tao; Fuchang Yu; Meng Qi; Shiwen Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

MOF-templated fabrication of Ni@C/g-C3N4 catalyst with high-dense accessible active sites achieving dicyclopentadiene hydrogenation at ambient conditions and comprehensive mechanism insight - Chenghong Wu; Xiaopeng Chen; Jiezhen Liang; Jiawei Fu; Zhongyao Zhang; Xiaojie Wei; Linlin Wang (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

A rapid and sensitive single-cell proteomic method based on fast liquid-chromatography separation, retention time prediction and MS1-only acquisition - Wei Fang; Zhuokun Du; Linlin Kong; Bin Fu; Guibin Wang; Yangjun Zhang; Weijie Qin (Analytica Chimica Acta, 2023)

Performance of wetland applied to ecological remediation of abandoned fish ponds: A case study in Gonghu Bay, Tai lake - Linlin Li; Jing Zhang; Shaoyong Lu; Hongbin Lu; Zhichao Du; Bin Bi; Fengmei Cao; Weijing Kong (Chemosphere, 2023)

Relationships between denitrification rates and functional gene abundance in a wetland: The roles of single- and multiple-species plant communities - Yushuang Kong; Haikuo Zhang; Linlin Tian; Junji Yuan; Youchao Chen; Yan Li; Jian Chen; Scott X. Chang; Yunying Fang; Ehsan Tavakkoli; Yanjiang Cai (Science of The Total Environment, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Rhizobacteria helps to explain the enhanced efficiency of phytoextraction strengthened by Streptomyces pactum - Linlin Wang; Nina Wang; Di Guo; Zhengzheng Shang; Yiying Zhang; Song Liu; Yuheng Wang (Journal of Environmental Sciences, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

Enhanced antihypertensive potential of fermented pomegranate juice: The contribution of phenolic compounds biotransformation and the resultant angiotensin-I-converting enzyme inhibition mechanism - Li Chen; Linlin Wang; Guowei Shu; Jiaojiao Yuan; Jiying Zhang; Shan Qin; Jianke Li (Food Chemistry, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Development of Zein/tannic acid nanoparticles as antioxidants for oxidation inhibition of blackberry seed oil emulsions - Shuangjian Li; Siyuan Li; Minhui Gong; Hongzhi Zhang; Linlin Fan; Xiaoli Liu; Jianzhong Zhou (Food Chemistry, 2023)

Selective recovery of lithium from spent LiFePO4 battery via a self-catalytic air oxidation method - Hao Jin; Jialiang Zhang; Cheng Yang; Linlin Ma; Yongqiang Chen; Chengyan Wang (Chemical Engineering Journal, 2023)

Upscaling of Se(IV) sorption coefficients with hierarchical mineral characterization in multi-scale fractured granite - Funing Ma; Xiaoying Zhang; Chuanjun Zhan; Wei Chen; Linlin Qi; Zhenxue Dai (Stochastic Environmental Research and Risk Assessment, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Straw type and returning amount affects SOC fractions and Fe/Al oxides in a rice-wheat rotation system - Linlin Dong; Haihou Wang; Yuan Shen; Lingqing Wang; Haidong Zhang; Linlin Shi; Changying Lu; Mingxing Shen (Applied Soil Ecology, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Comparison of nitrogen removal performance and mechanism from low-polluted wastewater by constructed wetlands with two oxygen supply strategies: Tidal flow and intermittent aeration - Linlin Li; Jing Zhang; Qiuyue Shi; Shaoyong Lu (Chemosphere, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Understanding the N-acylated homoserine lactones(AHLs)-based quorum sensing for the stability of aerobic granular sludge in the aspect of substrate hydrolysis enhancement - Zhiming Zhang; Linlin Wang; Yatong Ji; Runjuan Cao; Jiaheng Zhou; Mengyan Li; Liang Zhu; Xiangyang Xu (Science of The Total Environment, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Study on antibacterial mechanism of electron beam radiation on Aspergillus flavus - Linlin Fan; Lili Li; Feifei Shang; Yuhua Xie; Zhenhua Duan; Qianwei Cheng; Yuqiao Zhang (Food Bioscience, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Regulation of MIL-88B(Fe) to design FeS2 core-shelled hollow sphere as high-rate anode for a full sodium-ion battery - Linlin Ma; Baoxiu Hou; Hui Zhang; Shitao Yuan; Bin Zhao; Yuan Liu; Xinran Qi; Haiyan Liu; Shuaihua Zhang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Acrylamide Induces Neurotoxicity in SH-SY5Y Cells via NLRP3-mediated Pyroptosis - Mengyao Zhao; Boya Zhang; Linlin Deng; Liming Zhao (Molecular Neurobiology, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

microRNA-29b-3p/sirtuin-1/peroxisome proliferator–activated receptor γ suppress osteogenic differentiation - Huanxin Xie; Lei Cao; Linlin Ye; Qiang Li; Yaohua Zhang; Hongyue Zhang; Huaqing Yang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Geochronology and geochemistry of the Late Triassic intrusive rocks in the Liaodong Peninsula, NE China: Petrogenesis and implications for early Mesozoic tectonic evolution - Peng Zhang; Yan Zhao; Linlin Kou; Deming Sha (International Geology Review, 2023)

Synergistic relationship or not? Understanding the resilience and efficiency of the tourism economy: evidence from Hainan Province, China - Pengfei Zhang; Hu Yu; Linlin Xu; Wei Guo; Mingzhe Shen (Environment, Development and Sustainability, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

Two-stage chemical-biological oxidation process for low-grade refractory gold concentrate with high arsenic and sulfur - Shiqi Zhang; Hongying Yang; Linlin Tong; Pengcheng Ma; Zuochun Luan; Qifei Sun; Youqin Zhou (Minerals Engineering, 2023)

Responses and tolerance mechanisms of microalgae to heavy metal stress: A review - Xinfeng Xiao; Wenfang Li; Meng Jin; Linlin Zhang; Liguo Qin; Weiwei Geng (Marine Environmental Research, 2023)

Exploratory study on the potential regulating role of Peroxiredoxin 6 on proteolysis and relationships with desmin early postmortem - Xinyi Wang; Linlin Huang; Yimin Zhang; Lixian Zhu; Xiaoyin Yang; Huixin Zuo; Xin Luo; Yanwei Mao; David L. Hopkins (Meat Science, 2023)

Data quality evaluation and calibration of on-road remote sensing systems based on exhaust plumes - Shijie Liu; Xinlu Zhang; Linlin Ma; Liqiang He; Shaojun Zhang; Miaomiao Cheng (Journal of Environmental Sciences, 2023)

Genesis of the Xinfang gold deposit, Liaodong Peninsula: Constraints from fluid inclusions, H-O-S-Pb isotopes, pyrite trace element concentrations, and chronology - Peng Zhang; Yan Zhao; Linlin Kou; Hong zhi Yang (Gondwana Research, 2023)

Gas hydrate dissociation by depressurization along with ice occurrence and sand migration - Shicai Sun; Linlin Gu; Zhendong Yang; Haifei Lin; Changxing Zhang (Gas Science and Engineering, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Estimating small structural motions from multi-view video measurement - Enjian Cai; Yi Zhang; Xiaodong Ji; Xinzheng Lu; Linlin Xie; Yuncheng Zhuang; Taisen Zhao; Guangwei Lin (Engineering Structures, 2023)

Pseudo-isotopic substituted (Co0.5Ni0.5)S2 anchoring on V4C3T MXene as an efficient anode for full sodium-ions batteries - Yilin Li; J.M. Cao; Linlin Li; Zeyu Yuan; Dongdong Li; Junzhi Li; Yuming Zhang; Hao Xu; Wei Han; Lili Wang (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Investigation of the mechanism of copy number variations involving the α-globin gene cluster on chromosome 16: two case reports and literature review - Dina Zhu; Linlin Xu; Yanxia Zhang; Guanxia Liang; Xiaofeng Wei; Liyan Li; Wangjie Jin; Xuan Shang (Molecular Genetics and Genomics, 2023)

Fluoride-Induced Sperm Damage and HuR-Mediated Excessive Apoptosis and Autophagy in Spermatocytes - Yanyan Li; Jianbin Zhang; Linlin Sun; Hongyu Zhao; Xiaohan Jia; Yingri Zhang; Yuanbin Li (Biological Trace Element Research, 2023)

Divergent responses of Qinghai spruce (Picea crassifolia) to recent warming along elevational gradients in the central Qilian Mountains, Northwest China - Weiguo Zhang; Xiaohua Gou; Fen Zhang; Wenhuo Liu; Yun Zhang; Linlin Gao (Journal of Geographical Sciences, 2023)

Whether increased water‐use efficiency of Picea crassifolia promotes radial growth of trees in the eastern Qilian Mountains - Kai Wang; Xiaohua Gou; Linlin Gao; Wenhuo Liu; Haowen Fan; Weiguo Zhang; Haijiang Yang (International Journal of Climatology, 2022)
Global change, characterized by elevated atmospheric CO 2 concentrations and warming, is profoundly affecting terrestrial forests. However, whether the increasing atmospheric CO 2 concentration has a fertilizer effect on tree growth and whether intrinsic water use efficiency (iWUE) promotes tree growth in semi‐arid regions is not entirely clear. In this study, we evaluated the relationships between tree‐ring widths, δ 13 C values and iWUE of Qinghai Spruce ( Picea crassifolia Kom.) in the eastern Qilian Mountains, northwestern China. We found that the iWUE is significantly consistent with the δ 13 C of rings in the high‐frequency signal, and the relationship between iWUE and tree‐ring width is unstable. The first‐order difference correlation analysis with meteorological data showed that both the iWUE and tree‐ring width were drought‐limited. The radial growth was mainly regulated by water availability in current April and July, while annual variation of iWUE was primarily controlled by that in current July. In the early stage of trees growth, there was a positive relationship between iWUE and radial growth due to the CO 2 fertilization. During the 1970s–2000s, the effect of water availability in July on radial growth increases because of the decreased precipitation in July. This has decreased stomatal conductance, intercellular CO 2 concentration, carbon uptake and growth, contributing to the negatively significant correlation between tree‐ring widths and iWUE ( p

LncRNA OIP5-AS1 Mitigates Bupivacaine-Induced Neurotoxicity in Dorsal Root Ganglion Neurons Through Regulating NFAT5 Expression via Sponging miR-34b - Yina Yin; Min Ma; Junxiao Chang; Yufang Kong; Linlin Rui; Guoqiang Chu; Keliang Zhang (Neurotoxicity Research, 2022)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Improving precipitation ensemble forecasts of typhoon heavy rainfall over East China with a modified probability-matching technique - Chun Liu; Hanqing Deng; Xuexing Qiu; Linlin Zheng; Yajun Lu; Ying Zhang (Bulletin of Atmospheric Science and Technology, 2022)

Core rhizosphere microbiome of Panax notoginseng and its associations with belowground biomass and saponin contents - Guangfei Wei; Guozhuang Zhang; Mengzhi Li; Congsheng Liu; Fugang Wei; Yong Wang; Zhixin Huang; Zhongjian Chen; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Microbiology, 2022)
The core rhizosphere microbiome is critical for plant fitness. However, its contribution to the belowground biomass and saponin contents of Panax notoginseng remains unclear. High‐throughput sequencing of amplicon and metagenome was performed to obtain the microbiome profiles and functional traits in P. notoginseng rhizosphere across a large spatial scale. We obtained 639 bacterial and 310 fungal core OTUs, which were mainly affected by soil pH and organic matter (OM). The core taxa were grouped into four ecological clusters (i.e. high pH, low pH, high OM and low OM) for sharing similar habitat preferences. Furthermore, structural equation modelling (SEM) and correlation analyses revealed that the diversity and composition of core microbiomes, as well as the metagenome‐derived microbial functions, were related to belowground biomass and saponin contents. Key microbial genera related to the two plant indicators were also identified. In short, this study explored the main driving environmental factors of core microbiomes in the P. notoginseng rhizosphere and revealed that the core microbiomes and microbial functions potentially contributed to the belowground biomass and saponin contents of the plant. This work may enhance our understanding of interactions between microbes and perennial plants and improve our ability to manage root microbiota for the sustainable production of herbal medicine.

A decision-support system for recycling of residents’ waste plastics in China based on material flow analysis and life cycle assessment - Manzhi Liu; Jixin Wen; Linlin Zhang; Jixin Wu; Xiaotao Yang; Ying Qin; Yingjie Liu (Environmental Science and Pollution Research, 2022)

Three periods of gold mineralization in the Liaodong Peninsula, North China Craton - Peng Zhang; Linlin Kou; Yang Zhao (International Geology Review, 2022)

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

High levels of serum IL-10 indicate disease progression, extramedullary involvement, and poor prognosis in multiple myeloma - Xiaoyan Yue; Linlin Huang; Yang Yang; Yi Zhao; Donghua He; Xiaoyan Han; Gaofeng Zheng; Yi Li; Enfan Zhang; Zhen Cai; Xin Huang; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2022)

Surveillance of long-term environmental elements and PM2.5 health risk assessment in Yangtze River Delta, China, from 2016 to 2020 - Keqin Wu; Yuanhua Meng; Yan Gong; Xuhui Zhang; Linlin Wu; Xinliang Ding; Xiaofeng Chen (Environmental Science and Pollution Research, 2022)

Seasonal variability of the North Equatorial Current–Kuroshio Current–Mindanao Current based on observations - Fujun Wang; Linlin Zhang; Junqiao Feng; Dunxin Hu (Frontiers in Marine Science, 2022)
Utilizing the direct mooring observation along 130°E (10.5°N, 13°N, 15.5°N, and 18°N), 18°N (122.7°E, 123°E, and 123.3°E), and 8°N (127°E) and satellite data, the seasonal variabilities of the North Equatorial Current (NEC), Kuroshio Current (KC), and Mindanao Current (MC) were investigated. The southern part of the NEC along 130°E, the KC along 18°N, and the MC along 8°N featured similar seasonal cycles: that is, the currents were strong in spring and weak in autumn, while the KC along 18°N featured another peak in winter. Moreover, the seasonal phase of the NEC along 130°E was latitude-dependent; it advanced slightly from 10°N to 14°N and delayed poleward. The seasonal variabilities of the three currents were mainly controlled by local winds and Rossby waves via a geostrophic relationship, as the mooring observation was consistent with satellite data. The calculation shows that the local wind was dominant in the above mentioned in-phase areas (i.e., the southern part of the NEC, KC, and MC), while Rossby waves played an important role in the northern part of the NEC. The results indicate that the NEC–KC–MC system had the same zonal dynamics but different meridional dynamics across seasons.

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Interannual variations of the North Equatorial Current/Undercurrent from mooring array observations - Ying Huang; Linlin Zhang; Fujun Wang; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Interannual variability of the North Equatorial Current (NEC)/Undercurrent (NEUC) in the northwestern Pacific was investigated with the mooring array measurements at 130°E during 2014-2021, in combination with the satellite altimetry. Mooring observations indicate that the velocity of the NEC/NEUC in the upper 900 m exhibits significant variations on the interannual time scale. The westward-flowing NEC strengthens when the underlying eastward-flowing NEUC weakens, and the NEUC branch at 8.5°N is intensified during the mature phase of El Niño and reaches the maximum velocity during the decay phase of El Niño. The phase of the interannual variation of the currents delays with the increasing latitude, with the signal at 15°N lagging that at 8.5°N by about one year. Based on a 1.5 layer reduced gravity model, the interannual variation is suggested to be controlled mainly by the westward propagating baroclinic Rossby wave induced by the wind stress curl forcing in the central Pacific. Different propagating speed of the baroclinic Rossby wave at different latitudes explains the meridional phase lag of the interannual signal. Empirical Orthogonal Function and vertical mode decomposition analysis suggest that the interannual variation of the NEC/NEUC velocity in the northern part is dominated by surface-intensified signals with a vertical structure of the first baroclinic mode, while that in the southern part is dominated by subsurface-intensified signals which is associated with the combination of the first two baroclinic modes. The low-order mode baroclinic response of the ocean to the wind forcing accounts for the interannual fluctuation of the NEC/NEUC velocity observed by the mooring array.

The near-inertial waves observed east of the Philippines - Shengming Yuan; Xiaomei Yan; Linlin Zhang; Bing Yang; Chongguang Pang; Dunxin Hu (Journal of Oceanology and Limnology, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

AlgaeMask: An Instance Segmentation Network for Floating Algae Detection - Xiaoliang Wang; Lei Wang; Liangyu Chen; Feng Zhang; Kuo Chen; Zhiwei Zhang; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2022)
Video surveillance on the offshore booster station and around the coast is a effective way to monitor floating macroalgae. Previous studies on floating algae detection are mainly based on traditional image segmentation methods. However, these algorithms cannot effectively solve the problem of extracting Ulva prolifra and Sargassum at different sizes and views. Recently, instance segmentation methods have achieved great success in computer vision applications. In this paper, based on the CenterMask network, a novel instance segmentation architecture named AlgaeMask is proposed for floating algae detection from the surveillance videos. To address the feature extraction ability of the network in the inter-dependencies for position and channel, we introduce a new OSA-V3 module with the dual-attention block, which consists of a position attention mechanism and channel attention mechanism. Meanwhile, scale-equalizing pyramid convolution is introduced to solve the problem of scale difference. Finally, we introduce the feature decoder module based on FCOS head and segmentation head to obtain the segmentation area of floating algae in each bounding box. The extensive experiment results show that the average precision of our AlgaeMask in the tasks of mask segmentation and box detection can reach 44.22% and 48.13%, respectively, which has 15.09% and 8.24% improvement over CenterMask. In addition, the AlgaeMask can meet the real-time requirements of floating algae detection.

Health risk assessment of As due to rice ingestion based on iAs distribution and actual consumption patterns for the residents in Beijing: a cross-sectional study - Suzhen Cao; Qi Cao; Kan Shao; Yijin Kang; Weigang Liang; Linlin Zhang; Juan Wang; Ning Qin; Xiaoli Duan (Environmental Geochemistry and Health, 2022)

Radioactivity of Strontium-90 in Soil Samples Along the Hai River in Tianjin, China - Fei Chen; Linlin Yan; Qiang Xiong; Xiao Ge; Jing Liang; Zhen Zhang; Shengyuan Yang; Ling Jiao (Water, Air, & Soil Pollution, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

p53 m6A modulation sensitizes hepatocellular carcinoma to apatinib through apoptosis - Weiwei Ke; Linlin Zhang; Xiangxuan Zhao; Zaiming Lu (Apoptosis, 2022)

Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Wei Zhang; Yue Xu; Yu Xue; Linlin Zhang (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate . We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.

Metabolism and pharmacokinetics of mebendazole in Japanese pufferfish ( Takifugu rubripes ) - Lei Men; Yuhan Zhang; Keke Li; Zhongyu Li; Chunbin Li; Xueyuan Zhang; Xiaojie Gong; Linlin Fang (Food Additives & Contaminants: Part A, 2022)

Tsunami hazard assessment in the South China Sea: A review of recent progress and research gaps - Linlin Li; Qiang Qiu; Zhigang Li; Peizhen Zhang (Science China Earth Sciences, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

Two Flavors of Intraseasonal Variability and Their Dynamics in the North Equatorial Current/Undercurrent Region - Zhenxiao Wang; Linlin Zhang; Yuchao Hui; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Significant surface-intensified and subsurface-intensified intraseasonal variability (ISV) of the North Equatorial Current/Undercurrent with different periods are detected to coexist with mooring ADCP measurements at 13°N, 130°E. The ISV of the currents in the upper 200 m has a relatively shorter period of 45 days, while the period of the subsurface-intensified ISV between 400 and 800 m is around 85 days. By combining with sea surface height measurements from satellite altimeters and outputs from an eddy-resolving ocean general circulation model, the origin and dynamic mechanism of the two flavors of ISV are investigated. Eddy trajectory tracking and energy analysis indicate that both the surface-intensified and subsurface-intensified ISV are related to locally generated meso-scale eddies near the mooring sites. Stability analysis suggests the surface-intensified ISV is related to the baroclinic instability induced by the vertical velocity shear of the North Equatorial Current. While the generation of the subsurface-intensified ISV is more complex and is partly related to the enhanced barotropic instability induced by the intensified horizontal shear of the subsurface zonal background flow.

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

Genetic background and cis-organization regulate ALDH7B4 gene expression in Eutrema salsugineum: a promoter analysis case study - Quancan Hou; Tianye Zhang; Wei Zhao; Linlin Wang; Lu Lu; Yuchen Qi; Dorothea Bartels (Planta, 2022)

Correction to: Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; ·Wanyu Song; Ying Shi (Journal of Molecular Histology, 2022)

Characterizing the Semi-Volatile Organic Compounds in Runoff from Roads and Other Impervious Surfaces in a Suburban Area of Beijing - Liang Zhang; Haiyan Li; Youshu Wang; Zhichao Yang; Ziyang Zhang; Fei Liu; Linlin Tong; Ying Wang; Yongwei Gong; Hua Yang (Archives of Environmental Contamination and Toxicology, 2022)

Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Zunlei Liu; Yan Jin; Liping Yan; Yi Zhang; Hui Zhang; Chuyi Shen; Linlin Yang; Jiahua Cheng (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail ( Trichiurus japonicus ) has been over-exploited since the early 2000s. Therefore, the spatio-temporal management of largehead hairtail nursery grounds could effective help its recovery. This study aims to predict juvenile largehead hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent scientific survey data (Catch per unit effort, CPUE) and geographic/physical variables (Depth, Distance to the coast, Sea bottom temperature, Dissolved oxygen concentration and Net primary production) to analyze the probability of occurrence and abundance distribution of juvenile largehead hairtail. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability (AUC = 0.81) and abundance distribution ( r = 0.89) of juvenile largehead hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the East China Sea hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occurs outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing largehead hairtail conservation efforts in the East China Sea. We suggested that the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.

Effects of Smooth Cordgrass Spartina alterniflora Invasion on Macrobenthic Fauna in the Yellow River Delta - Shaoyu Jiang; Chuanxin Zhang; Linlin Chen; Chunyun Liu; Lang Yan; Baoquan Li (Wetlands, 2022)

Taxonomy and regeneration of a newly recorded Polychaete Capitella teleta (Annelida, Capitellidae) in the coastal water of Shandong, China - Qian Li; Yongnan Li; Yue Wang; Xuwen Wu; Linlin Zhang (Journal of Oceanology and Limnology, 2022)

Correction to: Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC‑7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Recent advances in functional 3D printing of foods: a review of functions of ingredients and internal structures - Linlin Zhao; Min Zhang; Bimal Chitrakar; Benu Adhikari (Critical Reviews in Food Science and Nutrition, 2021)

Functional Trait Responses of Macrobenthos to Anthropogenic Pressure in Three Temperate Intertidal Communities - Jian-Yu Dong; Linlin Zhao; Xiaolong Yang; Xin Sun; Xiumei Zhang (Frontiers in Marine Science, 2021)
With the increasing impact of human activities on marine ecosystems, there is a growing need to assess how the components of marine ecosystems (e.g., macrobenthos) respond to these anthropogenic pressures. In this work, the trait-based approach was used to assess the effects of anthropogenic pressures represented by the area of land-based aquaculture pond (Pond Area) and heavy metals on the macrobenthic communities in three intertidal zones[Aoshan Bay (AO), Wenquan River and Daren River (RW), and Xiaodao Bay (XD)] of Laoshan Bay, Shandong Peninsula, China. Compared with RW and XD, AO was under more pressure in terms of the average concentrations of heavy metals and total organic carbon (TOC) in sediments and also in the Pond Area. Fuzzy correspondence analysis (FCA) showed that there were significant differences in the composition of functional traits among the three regions (PERMANOVA; p < 0.05). In the highly polluted area, macrobenthic communities exhibited a combination of traits, such as relatively short life span, weak mobility, feeding on deposits, and more tolerant to organic matter, whereas in a less polluted area, they exhibited a combination of traits, such as relatively long life span, relatively high mobility, and more sensitivity to organic matter. The RDA results showed that the distribution of the trait modalities was significantly affected by heavy metals (Hg and Cd), TOC, Pond Area, and sampled location. Variation partitioning analysis (VPA) indicated that the shared influence of sediment-related pollution factors and Pond Area contributed most to the variance of the functional traits, which implied that human activities directly and/or indirectly lead to changes in functional traits of macrobenthic communities in the intertidal zones.

Enhanced Phytoremediation of Soil Heavy Metal Pollution and Commercial Utilization of Harvested Plant Biomass: a Review - Samuel De-Graft Quarshie; Xinfeng Xiao; Linlin Zhang (Water, Air, & Soil Pollution, 2021)

Influence of Initial Stress and Deformation States on the Shear Creep Behavior of Rock Discontinuities with Different Joint Roughness Coefficients - Zhen Wang; Linlin Gu; Qingzhao Zhang; Bo-An Jang (Rock Mechanics and Rock Engineering, 2021)

Large-Eddy Simulation of Cavitating Tip Leakage Vortex Structures and Dynamics around a NACA0009 Hydrofoil - Linlin Geng; Desheng Zhang; Jian Chen; Xavier Escaler (Journal of Marine Science and Engineering, 2021)
The tip leakage vortex (TLV) has aroused great concern for turbomachine performance, stability and noise generation as well as cavitation erosion. To better understand structures and dynamics of the TLV, large-eddy simulation (LES) is coupled with a homogeneous cavitation model to simulate the cavitation flow around a NACA0009 hydrofoil with a given clearance. The numerical results are validated by comparisons with experimental measurements. The results demonstrate that the present LES can well predict the mean behavior of the TLV. By visualizing the mean streamlines and mean streamwise vorticity, it shows that the TLV dominates the end-wall vortex structures, and that the generation and evolution of the other vortices are found to be closely related to the development of the TLV. In addition, as the TLV moves downstream, it undergoes an interesting progression, i.e., the vortex core radius keeps increasing and the axial velocity of vortex center experiences a conversion from jet-like profile to wake-like profile.

Experimental and numerical investigation on the influence of PC window beam on the seismic performance of PC shear wall structures - Linlin Xie; Xun Chong; Lanfang Zhang; Xianguo Ye; Qing Jiang; Decai Wang (European Journal of Environmental and Civil Engineering, 2021)

Characteristics of Plastic Pollution in the Environment: A Review - Penghui Li; Xiaodan Wang; Min Su; Xiaoyan Zou; Linlin Duan; Hongwu Zhang (Bulletin of Environmental Contamination and Toxicology, 2021)

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC-7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

Estimation of the SARS-CoV-2 transmission probability in confined traffic space and evaluation of the mitigation strategies - Linlin Chen; Guangze Ban; Enshen Long; Gretchen Kalonji; Zhu Cheng; Li Zhang; Shurui Guo (Environmental Science and Pollution Research, 2021)

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

Effects of sodium arsenite and dimethyl arsenic acid on Liaoning cashmere goat skin fibroblasts - Fengqin Zhao; Chuang Wang; Dongyu Sun; Linlin Zhang; Zhiyue Wang; Jun Piao; Jingai Piao; Mei Jin (Environmental Science and Pollution Research, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Constitutive activation of β-catenin in odontoblasts induces aberrant pulp calcification in mouse incisors - Shijian Deng; Linlin Fan; Yunfei Wang; Qi Zhang (Journal of Molecular Histology, 2021)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Integrated analysis of miRNA and mRNA transcriptomic reveals antler growth regulatory network - Boyin Jia; Linlin Zhang; Yifan Zhang; Chenxia Ge; Fuhe Yang; Rui Du; Hengxing Ba (Molecular Genetics and Genomics, 2021)

Effect of divalent manganese (Mn2+) concentration on the growth and nitrate nitrogen content of lettuce during aeroponic intercropping with cherry radish - Lei Zhang; Linlin Wang; Faqinwei Li; Fei Xiao; Haiye Yu (Horticulture, Environment, and Biotechnology, 2021)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.

Comparison of Class 2 Integron Integrase Activities - Xiaotong Wang; Nana Kong; Mei Cao; Long Zhang; Muzhen Sun; Linlin Xiao; Gang Li; Quhao Wei (Current Microbiology, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Removal of ammonia nitrogen from water by mesoporous carbon electrode–based membrane capacitance deionization - Guiju Li; Yaning Cao; Zhen Zhang; Linlin Hao (Environmental Science and Pollution Research, 2021)

Black Soldier Fly (Hermetia illucens) Larvae Significantly Change the Microbial Community in Chicken Manure - Xingxiao Zhang; Junzhe Zhang; Linlin Jiang; Xin Yu; Hongwei Zhu; Jianlong Zhang; Zhibin Feng; Xiang Zhang; Guozhong Chen; Zhijian Zhang (Current Microbiology, 2021)

Seasonal variation of net ecosystem CO2 exchange and its influencing factors in an apple orchard in the Loess Plateau - Jianfeng Yang; Yumin Duan; Linlin Wang; Dan Kang; Mukesh Kumar Awasthi; Huike Li; Linsen Zhang (Environmental Science and Pollution Research, 2020)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

Three dimensional convolutional neural network-based classification of conduct disorder with structural MRI - Jianing Zhang; Xuechen Li; Yuexiang Li; Mingyu Wang; Bingsheng Huang; Shuqiao Yao; Linlin Shen (Brain Imaging and Behavior, 2020)

Colloidal gold-based immunochromatographic strip assay for the rapid detection of diminazene in milk - Linlin Chen; Yaning Sun; Xiaofei Hu; Yunrui Xing; Sharon Kwee; Guanqiong Na; Gaiping Zhang (Food Additives & Contaminants: Part A, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Instability in boundary layer between the North Equatorial Current and underlying zonal jets based on mooring observations - Fujun Wang; Junqiao Feng; Qingye Wang; Linlin Zhang; Shijian Hu; Dunxin Hu (Journal of Oceanology and Limnology, 2020)

Towards a revised framework of modified time series InSAR for mapping land deformation - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Qi Zhang (Journal of Geodesy, 2020)

Streptomyces albicerus sp. nov., a novel actinomycete isolated from the sediments of the Tailan River in Xinjiang, China - Beibei Sun; Linlin Yuan; Zhanfeng Xia; Chuanxing Wan; Lili Zhang (Archives of Microbiology, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

An Improved Coal Permeability Model with Variable Cleat Width and Klinkenberg Coefficient - Gang Wang; Zhiyong Xiao; Junhong Yu; Lu Zhang; Linlin Sun (Geotechnical and Geological Engineering, 2020)

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

Comparison of different soil dielectric models for microwave soil moisture retrievals - Linlin Zhang; Qingyan Meng; Die Hu; Ying Zhang; Shun Yao; Xu Chen (International Journal of Remote Sensing, 2020)

Creep characteristics and prediction of creep failure of rock discontinuities under shearing conditions - Zhen Wang; Linlin Gu; Qingzhao Zhang; Songlin Yue; Guokai Zhang (International Journal of Earth Sciences, 2020)

Variability of voriconazole concentrations in patients with hematopoietic stem cell transplantation and hematological malignancies: influence of loading dose, procalcitonin, and pregnane X receptor polymorphisms - Guangting Zeng; Linlin Wang; Lihong Shi; Huilan Li; Miaomiao Zhu; Jia Luo; Zanling Zhang (European Journal of Clinical Pharmacology, 2020)

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Low shear stress damages endothelial function through STAT1 in endothelial cells (ECs) - Linlin Zhu; Feng Wang; Hongfeng Yang; Junjie Zhang; Shaoliang Chen (Journal of Physiology and Biochemistry, 2020)

Four superoxide dismutases of Bacillus cereus 0–9 are non-redundant and perform different functions in diverse living conditions - Juanmei Zhang; Haodong Wang; Qiubin Huang; Ying Zhang; Linlin Zhao; Fengying Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2020)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Sulfate-enhanced degradation of Rhodamine B in the hydrogen peroxide/hydroxylamine system - Shengli Wang; Linlin Yan; Xiaohui Guan; Yanping Jia; Lianfa Song; Haifeng Zhang (Environmental Chemistry Letters, 2019)

Effects of Vitamin E and Selenium on Growth Performance, Antioxidant Capacity, and Metabolic Parameters in Growing Furring Blue Foxes (Alopex lagopus) - Keyuan Liu; Hanlu Liu; Ting Zhang; Linlin Mu; Xueqing Liu; Guangyu Li (Biological Trace Element Research, 2019)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

Spatiotemporal variability and trends in the hydrology of the Xiang River basin, China: extreme precipitation and streamflow - Juan Du; Linlin Cheng; Qiang Zhang (Arabian Journal of Geosciences, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Exploration of the key functional strains from an azo dye degradation microbial community by DGGE and high-throughput sequencing technology - Yan Chen; Lizhen Zhang; Linlin Feng; Guotao Chen; Yuanxiu Wang; Zhijun Zhai; Qinghua Zhang (Environmental Science and Pollution Research, 2019)

Diversity of the Fusarium pathogens associated with crown rot in the Huanghuai wheat‐growing region of China - Haifeng Zhou; Xiaolun He; Shuo Wang; Qingzhou Ma; Bingjian Sun; Shengli Ding; Linlin Chen; Meng Zhang; Honglian Li (Environmental Microbiology, 2019)
Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensis was isolated from the disease specimens and tested for virulence to wheat. The result of the pathogenicity revealed that an intraspecific differentiation existed in F. pseudograminearum ; sequence analysis of the EF‐1α gene showed that 194 F. pseudograminearum isolates were differentiated into two distinct clades which closed to the strains from Australia and China respectively, but neither pathogenicity nor EF‐1α sequence was related to the geographic origins of these isolates. However, universal rice primers‐polymerase chain reaction showed a correlation with the geographical origins of the 194 isolates, which were divided into eight subclusters, the level of genetic diversity was higher within a geographical population than among the different populations. The results of these analyses can be directly used to facilitate disease monitoring and development of control strategies.

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Geochemical characteristics of dust aerosol availability in northwestern China - Xunming Wang; Jimin Sun; Mingrui Qiang; Caixia Zhang; Danfeng Li; Ting Hua; Hui Li; Lili Lang; Linlin Jiao; Diwen Cai; Wenyong Ma (Arabian Journal of Geosciences, 2019)

Classification and characterization of bound water in marine mucky silty clay - Shuo Li; Changming Wang; Xianwei Zhang; Linlin Zou; Zhenxue Dai (Journal of Soils and Sediments, 2019)

Who cares what parents think or do? Observational learning and experience-based learning through communication in rice farmers’ willingness to adopt sustainable agricultural technologies in Hubei Province, China - Yangmei Zeng; Junbiao Zhang; Ke He; Linlin Cheng (Environmental Science and Pollution Research, 2019)

Formula of bed-load transport based on the total threshold probability - Linlin Li; Genguang Zhang; Jiajun Zhang (Environmental Fluid Mechanics, 2019)

Plastic Mulch and Plant Density Influencing Soil Water Content and Yield of Rainfed Maize in North‐Eastern China - Shijun Sun; Zhijun Chen; Hao Jiang; Xudong Zhang; Linlin Zhang; Daocai Chi (Irrigation and Drainage, 2019)
Plastic mulch, in combination with high plant density, is a common practice for rainfed maize production in north‐eastern China. However, the influence of these practices on soil water storage, maize yield and maize water productivity in different precipitation years is not well understood. In this paper, a 3‐year split‐plot field experiment was designed to compare non‐mulching and plastic film mulching in maize at 67 500 and 82 500 plants per ha in 2013, 2014 and 2015, and also 97 500 plants per ha in 2014 and 2015. Results revealed an increasing trend of precipitation in the study area from 1962 to 2015 and that the number of dry years and extreme years (including extreme dry and wet years) was increasing. In the moderately wet year 2013 and the moderately dry year 2015, the combination of 82 500 plants per ha and plastic film mulching produced the highest yield and water productivity (8.2 t ha −1 , 1.7 kg m −3 and 8.3 t ha −1 , 2.3 kg m −3 , respectively) for maize, while in the extremely dry year 2014 the highest yield (5.6 t ha −1 ) occurred with 97 500 plants per ha and non‐mulching. This research might be helpful for smallholder farmers needing optimal agricultural strategies to improve maize production in rainfed areas of north‐east China. © 2018 John Wiley & Sons, Ltd.

MiR-449a-5p mediates mitochondrial dysfunction and phenotypic transition by targeting Myc in pulmonary arterial smooth muscle cells - Chen Zhang; Cui Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Mingfei Ma; Xiaodong Zheng; Min Mao; Tingting Shen; Daling Zhu (Journal of Molecular Medicine, 2019)

Identification of protein arginine methyltransferase 7 (PRMT7) inhibitor by virtual screening and biological evaluation in vitro - Linlin Liu; Xiaoning Kai; Qingqing Chen; Ling Zhang; Ruosi Yao; Jian Gao (Medicinal Chemistry Research, 2019)

Effect of supersaturation on the oral bioavailability of paclitaxel/polymer amorphous solid dispersion - Linlin Miao; Yuheng Liang; Wenli Pan; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Xing Tang (Drug Delivery and Translational Research, 2019)

Heat Transfer in Sandstones at Low Temperature - Zhiqiang Liu; Linlin Wang; Bo Zhao; Jingyi Leng; Guangqing Zhang; Diansen Yang (Rock Mechanics and Rock Engineering, 2019)

Ascorbic acid induces cardiac differentiation of white adipose tissue-derived stem cells - Wenhui Liu; Huan Liu; Yinghui Wang; Linlin Zhang; Chunhui Wang; Haifang Li (Molecular and Cellular Biochemistry, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Development of genome-wide SNPs for population genetics of Collichthys lucidus - Linlin Zhao; Meijie Jiang; Fangyuan Qu; Dan Yi; Shouqiang Wang; Zhaohui Zhang (Conservation Genetics Resources, 2018)

Effects of artificial aeration and iron inputs on the transformation of carbon and phosphorus in a typical wetland soil - Linlin Zhang; Ze Tang; Sijian Zhang; Xueying Jia; Xiaofei Yu; Guangzhi Sun; Yuanchun Zou (Journal of Soils and Sediments, 2018)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

Insight into the effects of biochar as adsorbent and microwave receptor from one-step microwave pyrolysis of sewage sludge - Jun Zhang; Yu Tian; Linlin Yin; Jie Zhang; Jörg E. Drewes (Environmental Science and Pollution Research, 2018)

Analyzing Coastal Wetland Degradation and its Key Restoration Technologies in the Coastal Area of Jiangsu, China - Linlin Cui; Guosheng Li; Ninglei Ouyang; Fengyun Mu; Fu Yan; Youtian Zhang; Xiaoyang Huang (Wetlands, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

Osteoprotegerin deficiency causes morphological and quantitative damage in epithelial rests of Malassez - Yunfei Wang; Mengmeng Liu; Shijian Deng; Xin Sui; Linlin Fan; Qi Zhang (Journal of Molecular Histology, 2018)

Wnt/β-catenin signaling pathway in severe preeclampsia - Xiaofang Wang; Zhan Zhang; Xianxu Zeng; Jinming Wang; Linlin Zhang; Wanyu Song; Ying Shi (Journal of Molecular Histology, 2018)

Difference of acute dissociation and 1-day culture on the electrophysiological properties of rat dorsal root ganglion neurons - Yuanlong Song; Miaomiao Zhang; Xiaoqing Tao; Zifen Xu; Yunjie Zheng; Minjie Zhu; Liangpin Zhang; Jinhan Qiao; Linlin Gao (Journal of Physiology and Biochemistry, 2018)

The decreased expression of Stat3 and p-Stat3 in preeclampsia-like rat placenta - Zhan Zhang; Xiaofang Wang; Jinming Wang; Linlin Zhang (Journal of Molecular Histology, 2018)

Seismic behavior of breakwaters on complex ground by numerical tests: Liquefaction and post liquefaction ground settlements - Linlin Gu; Feng Zhang; Xiaohua Bao; Zhenming Shi; Guanlin Ye; Xianzhang Ling (Earthquake Engineering and Engineering Vibration, 2018)

Iron Regulation of Wetland Vegetation Performance Through Synchronous Effects on Phosphorus Acquisition Efficiency - Xueying Jia; Zhijie Tian; Lei Qin; Linlin Zhang; Yuanchun Zou; Ming Jiang; Xianguo Lyu (Chinese Geographical Science, 2018)

Time-Dependent Lactate Production and Amino Acid Utilization in Cultured Astrocytes Under High Glucose Exposure - Dan Wang; Liangcai Zhao; Hong Zheng; Minjian Dong; Linlin Pan; Xi Zhang; Huajie Zhang; Hongchang Gao (Molecular Neurobiology, 2018)

Influence of polymeric carrier on the disposition and retention of 20(R)-ginsenoside-rg3-loaded swellable microparticles in the lung - Xiuhua Wang; Xiao Zhang; Linlin Fan; Huan He; Xiaofei Zhang; Yuyang Zhang; Shirui Mao (Drug Delivery and Translational Research, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

Characterizing the interactions of two lipid modifications with lipid rafts: farnesyl anchors vs. palmitoyl anchors - Tao Zhang; Qichao Luo; Linlin Yang; Hualiang Jiang; Huaiyu Yang (European Biophysics Journal, 2018)

Co-Delivery of Doxorubicin and Survivin shRNA-Expressing Plasmid Via Microenvironment-Responsive Dendritic Mesoporous Silica Nanoparticles for Synergistic Cancer Therapy - Zhengxiong Li; Linlin Zhang; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2017)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

The vertical structure and variability of the western boundary currents east of the Philippines: case study from in situ observations from December 2010 to August 2014 - Fujun Wang; Linlin Zhang; Dunxin Hu; Qingye Wang; Fangguo Zhai; Shijian Hu (Journal of Oceanography, 2017)

Identification and Functional Analysis of Two Cotton Orthologs of MAX2 Which Control Shoot Lateral Branching - Linlin Zhao; Jingjing Fang; Jin Xing; Weina Liu; Peng Peng; Haixin Long; Jinfeng Zhao; Wenhui Zhang; Xueyong Li (Plant Molecular Biology Reporter, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

A lncRNA promotes myoblast proliferation by up-regulating GH1 - Yingwei Yue; Congfei Jin; Mingming Chen; Linlin Zhang; Xinfeng Liu; Wenzhi Ma; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Spatiotemporal drought variability of the eastern Tibetan Plateau during the last millennium - Yang Deng; Xiaohua Gou; Linlin Gao; Meixue Yang; Fen Zhang (Climate Dynamics, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Investigation on the removal of H2S from microwave pyrolysis of sewage sludge by an integrated two-stage system - Jun Zhang; Yu Tian; Linlin Yin; Wei Zuo; Zhenlong Gong; Jie Zhang (Environmental Science and Pollution Research, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

Settlement mechanism of piled-raft foundation due to cyclic train loads and its countermeasure - Linlin Gu; Guanlin Ye; Zhen Wang; Xianzhang Ling; Feng Zhang (Earthquake Engineering and Engineering Vibration, 2017)

Staphylococcus enterotoxin profile of China isolates and the superantigenicity of some novel enterotoxins - Menglu Shen; Yi Li; Linlin Zhang; Songbao Dai; Jiashun Wang; Yongqing Li; Lei Zhang; Jinhai Huang (Archives of Microbiology, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

Assessing the influences of tree species, elevation and climate on tree-ring growth in the Qilian Mountains of northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Meixue Yang; Fen Zhang (Trees, 2017)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

Identification of forty-five gene-derived polymorphic microsatellite loci for the sea cucumber, Apostichopus japonicus - MENG CHEN; LINLIN GAO; WEIJIE ZHANG; HONGZHENG YOU; QIAN SUN; YAQING CHANG (Journal of Genetics, 2016)

Genome-Wide Analysis of Alternative Splicing Provides Insights into Stress Adaptation of the Pacific Oyster - Baoyu Huang; Linlin Zhang; Xueying Tang; Guofan Zhang; Li Li (Marine Biotechnology, 2016)

Selenium Deficiency Influences the Expression of Selenoproteins and Inflammatory Cytokines in Chicken Aorta Vessels - Qiang Du; Haidong Yao; Linlin Yao; Ziwei Zhang; Xingen Lei; Shiwen Xu (Biological Trace Element Research, 2016)

Trivalent chromium alleviates oleic acid induced steatosis in SMMC-7721 cells by decreasing fatty acid uptake and triglyceride synthesis - Song Wang; Jian Wang; Xiaonan Zhang; Linlin Hu; Zhijia Fang; Zhiwei Huang; Ping Shi (BioMetals, 2016)

Probing the structure and dynamics of caveolin-1 in a caveolae-mimicking asymmetric lipid bilayer model - Hanqi Liu; Linlin Yang; Qiansen Zhang; Lingxue Mao; Hualiang Jiang; Huaiyu Yang (European Biophysics Journal, 2016)

Hazard posed by metals and As in PM2.5 in air of five megacities in the Beijing-Tianjin-Hebei region of China during APEC - Linlin Zhang; Xiaowei Jin; Andrew C. Johnson; John P. Giesy (Environmental Science and Pollution Research, 2016)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

Tree‐ring recorded drought variability in the northern Min Mountains of northwestern China - Yang Deng; Xiaohua Gou; Linlin Gao; Fen Zhang; Xiangyu Xu; Meixue Yang (International Journal of Climatology, 2016)
Drought is a recurrent natural disaster in northwestern China and it can have a substantial impact on the affected region; therefore, knowledge of drought variability is very important for drought adaptation and mitigation. However, the observed climate data are generally limited in length, which may hamper our understanding the full range of drought variability. Using tree‐ring width measurements of 155 series from 81 Pinus tabulaeformis trees at three sites in the northern Min Mountains of northwestern China, the standardized precipitation evapotranspiration index ( SPEI ) for May–August from 1804 to 2011 were reconstructed, which account for 64.8% of the variance in the instrumental record over 1954–2011. The new reconstruction is generally consistent with other moisture reconstructions nearby. Two notable features of the SPEI reconstruction is the severe drought starting in the late 1990s and the gradual drying trend since 1954. These features are also apparent in areas located in the north boundaries of Eastern Asian Summer Monsoon ( EASM ), which indicates that the study area may be affected by the EASM .

Reactive oxygen species effect PASMCs apoptosis via regulation of dynamin-related protein 1 in hypoxic pulmonary hypertension - Lixin Zhang; Cui Ma; Chen Zhang; Mingfei Ma; Fengying Zhang; Linlin Zhang; Yingli Chen; Fangyuan Cao; Shuzhen Li; Daling Zhu (Histochemistry and Cell Biology, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Zircon ages and Hf isotopic compositions of Permian and Triassic A-type granites from central Inner Mongolia and their significance for late Palaeozoic and early Mesozoic evolution of the Central Asian Orogenic Belt - Yuruo Shi; J. Lawford Anderson; Linlin Li; Jing Ding; Cui Liu; Wei Zhang; Chonghui Shen (International Geology Review, 2016)

Spatial and Seasonal Variations of Polycyclic Aromatic Hydrocarbons (PAHs) in Ambient Particulate Matter (PM10, PM2.5) in Three Mega-Cities in China and Identification of Major Contributing Source Types - Linlin Zhang; Rui Chen; Jungang Lv (Bulletin of Environmental Contamination and Toxicology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Expression Characterization of Stress Genes Under High and Low Temperature Stresses in the Pacific Oyster, Crassostrea gigas - Qihui Zhu; Linlin Zhang; Li Li; Huayong Que; Guofan Zhang (Marine Biotechnology, 2016)

Bioinformatics analyses of Shigella CRISPR structure and spacer classification - Pengfei Wang; Bing Zhang; Guangcai Duan; Yingfang Wang; Lijuan Hong; Linlin Wang; Xiangjiao Guo; Yuanlin Xi; Haiyan Yang (World Journal of Microbiology and Biotechnology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Forward modeling analyses of Qilian Juniper (Sabina przewalskii) growth in response to climate factors in different regions of the Qilian Mountains, northwestern China - Junzhou Zhang; Xiaohua Gou; Yongxiang Zhang; Ming Lu; Xiangyu Xu; Fen Zhang; Wenhuo Liu; Linlin Gao (Trees, 2016)

Gene transcript profiles in the desert plant Nitraria tangutorum during fruit development and ripening - Jia Wang; Zhenhua Dang; Huirong Zhang; Linlin Zheng; Tebuqin Borjigin; Yingchun Wang (Molecular Genetics and Genomics, 2016)

Effects of Single and Joint Subacute Exposure of Copper and Cadmium on Heat Shock Proteins in Common Carp (Cyprinus carpio) - Xuyang Jiang; Xueting Guan; Linlin Yao; Hong Zhang; Xian Jin; Ying Han (Biological Trace Element Research, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Event-related potentials elicited by social commerce and electronic-commerce reviews - Yan Bai; Zhong Yao; Fengyu Cong; Linlin Zhang (Cognitive Neurodynamics, 2015)

The effects of commercial microbial agents (probiotics) on phytoplankton community structure in intensive white shrimp (Litopenaeus vannamei) aquaculture ponds - Betina Lukwambe; Linlin Qiuqian; Jinfeng Wu; Demin Zhang; Kai Wang; Zhongming Zheng (Aquaculture International, 2015)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Millennium tree-ring reconstruction of drought variability in the eastern Qilian Mountains, northwest China - Xiaohua Gou; Yang Deng; Linlin Gao; Fahu Chen; Edward Cook; Meixue Yang; Fen Zhang (Climate Dynamics, 2015)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

Analysis of the temporal and spatial distribution of water quality in China’s major river basins, and trends between 2005 and 2010 - Jinjian Li; Xiaojie Meng; Yan Zhang; Juan Li; Linlin Xia; Hongmei Zheng (Frontiers of Earth Science, 2015)

A gyrovirus infecting a sea bird - Linlin Li; Patricia A. Pesavento; Anne M. Gaynor; Rebecca S. Duerr; Tung Gia Phan; Wen Zhang; Xutao Deng; Eric Delwart (Archives of Virology, 2015)

Heavy mineral assemblage characteristics and the Cenozoic paleogeographic evolution in southwestern Qaidam Basin - LinLin Li; ZhaoJie Guo; ShuWei Guan; SuPing Zhou; MingZhen Wang; YaNan Fang; ChenChen Zhang (Science China Earth Sciences, 2015)

Integrated Approach Based on a Regional Habitat Succession Model to Assess Wetland Landscape Ecological Degradation - Linlin Cui; Guosheng Li; Huajun Liao; Ninglei Ouyang; Yue Zhang (Wetlands, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Expression of neuropeptides and bone remodeling-related factors during periodontal tissue regeneration in denervated rats - Xijiao Yu; Linlin Lv; Jing Zhang; Ting Zhang; Changjie Xiao; Shu Li (Journal of Molecular Histology, 2015)

Roles of oxidative stress and endoplasmic reticulum stress in selenium deficiency-induced apoptosis in chicken liver - Linlin Yao; Qiang Du; Haidong Yao; Xi Chen; Ziwei Zhang; Shiwen Xu (BioMetals, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Identification and characteristics of imipenem-resistant Acinetobacter baumannii in surgical wards in a Chinese university hospital - Dalin Wang; Linlin Ma; Zhenyu Wu; Mingcheng Li; Xiaohan Li; Wei Zhang; Kun Chen (Infectious Diseases, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Comparative analysis of oyster ( Crassostrea gigas ) immune responses under challenge by different Vibrio strains and conditions - Jie Meng; Linlin Zhang; Baoyu Huang; Li Li; Guofan Zhang (Molluscan Research, 2015)

Selenium Deficiency Influences the Gene Expressions of Heat Shock Proteins and Nitric Oxide Levels in Neutrophils of Broilers - Xi Chen; Haidong Yao; Linlin Yao; Jinxin Zhao; Yilin Luan; Ziwei Zhang; Shiwen Xu (Biological Trace Element Research, 2014)

Study on Evolution Features and Spatial Distribution Patterns of Coastal Wetlands in North Jiangsu Province, China - Huajun Liao; Guosheng Li; Linlin Cui; Ninglei Ouyang; Yue Zhang; Shaohua Wang (Wetlands, 2014)

Alternative splicing and immune response of Crassostrea gigas tumor necrosis factor receptor-associated factor 3 - Baoyu Huang; Linlin Zhang; Yishuai Du; Li Li; Tao Qu; Jie Meng; Guofan Zhang (Molecular Biology Reports, 2014)

Overexpression of the PLAP-1 gene inhibits the differentiation of BMSCs into osteoblast-like cells - Jing Sun; Ting Zhang; Panpan Zhang; Linlin Lv; Yanzhi Wang; Jing Zhang; Shu Li (Journal of Molecular Histology, 2014)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

CRISPR/Cas technology: a revolutionary approach for genome engineering - LinLin Zhang; Qi Zhou (Science China Life Sciences, 2014)

Healing of periodontal defects and calcitonin gene related peptide expression following inferior alveolar nerve transection in rats - Linlin Lv; Yanzhi Wang; Jing Zhang; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Cloning and functional analysis of two flavanone-3-hydroxylase genes from Reaumuria trigyna - Huirong Zhang; Lixia Zhao; Jia Wang; Linlin Zheng; Zhenhua Dang; Yingchun Wang (Acta Physiologiae Plantarum, 2014)

Organochlorine pesticide contamination in marine organisms of Yantai coast, northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Environmental Monitoring and Assessment, 2014)

Transcriptome Analysis Reveals a Rich Gene Set Related to Innate Immunity in the Eastern Oyster (Crassostrea virginica) - Linlin Zhang; Li Li; Yabing Zhu; Guofan Zhang; Ximing Guo (Marine Biotechnology, 2014)

The characteristics of epithelial cell rests of Malassez during tooth eruption of development mice - Yanzhi Wang; Linlin Lv; Xijiao Yu; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Isolation and characterization of a Δ1-pyrroline-5-carboxylate synthetase (NtP5CS) from Nitraria tangutorum Bobr. and functional comparison with its Arabidopsis homologue - Linlin Zheng; Zhenhua Dang; Haoyu Li; Huirong Zhang; Shubiao Wu; Yingchun Wang (Molecular Biology Reports, 2014)

Effects of Exogenous Salicylic Acid and Nitric Oxide on Physiological Characteristics of Perennial Ryegrass Under Cadmium Stress - Quanhui Wang; Xue Liang; Yuanjie Dong; Linlin Xu; Xiuwei Zhang; Jing Kong; Shuang Liu (Journal of Plant Growth Regulation, 2013)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

A robust regression-based linear model adjustment method for SAR interferogram stacking techniques - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (International Journal of Remote Sensing, 2013)

Polybrominated Diphenyl Ethers Contamination in Marine Organisms of Yantai Coast, Northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Bulletin of Environmental Contamination and Toxicology, 2013)

Life cycle assessment of composite packaging waste management—a Chinese case study on aseptic packaging - Minghui Xie; Qi Qiao; Qihong Sun; Linlin Zhang (The International Journal of Life Cycle Assessment, 2013)

Monitoring ground surface deformation over the North China Plain using coherent ALOS PALSAR differential interferograms - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (Journal of Geodesy, 2013)

Influence of algal bloom degradation on nutrient release at the sediment–water interface in Lake Taihu, China - Mengyuan Zhu; Guangwei Zhu; Linlin Zhao; Xin Yao; Yunlin Zhang; Guang Gao; Boqiang Qin (Environmental Science and Pollution Research, 2013)

Fosmid library construction and end sequences analysis of the Pacific oyster, Crassostrea gigas - Linlin Zhang; Li Li; Fei Xu; Haigang Qi; Xiaotong Wang; Huayong Que; Guofan Zhang (Molluscan Research, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Heavy metal contamination in the marine organisms in Yantai coast, northern Yellow Sea of China - Gaosheng Zhang; Dongyan Liu; Huifeng Wu; Linlin Chen; Qingxi Han (Ecotoxicology, 2012)

Elements in Lung Tissues of Patients from a High Lung Cancer Incidence Area of China - Linlin Zhang; Jungang Lv; Shengkun Sun (Biological Trace Element Research, 2012)

Monitoring ground deformation in Beijing, China with persistent scatterer SAR interferometry - Alex Hay-Man Ng; Linlin Ge; Xiaojing Li; Kui Zhang (Journal of Geodesy, 2012)

Dietary Exposure Estimates of 14 Trace Elements in Xuanwei and Fuyuan, Two High Lung Cancer Incidence Areas in China - Linlin Zhang; Jungang Lv; Chunyang Liao (Biological Trace Element Research, 2012)

Effect of mechanical stretch on the expressions of elastin, LOX and Fibulin-5 in rat BMSCs with ligament fibroblasts co-culture - Zhao Bing; Liang Linlin; Yan Jianguo; Ren Shenshen; Ren Ruifang; Zhang Xi (Molecular Biology Reports, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

Deformation mapping in three dimensions for underground mining using InSAR – Southern highland coalfield in New South Wales, Australia - Alex Hay-Man Ng; Linlin Ge; Kui Zhang; Hsing-Chung Chang; Xiaojing Li; Chris Rizos; Makoto Omura (International Journal of Remote Sensing, 2011)

Identification and Analysis of Muscle-Related Protein Isoforms Expressed in the White Muscle of the Mandarin Fish (Siniperca chuatsi) - Guoqiang Zhang; Wuying Chu; Songnian Hu; Tao Meng; Linlin Pan; Renxue Zhou; Zhen Liu; Jianshe Zhang (Marine Biotechnology, 2011)

The carboxyl terminal of the archaeal nuclease NurA is involved in the interaction with single-stranded DNA-binding protein and dimer formation - Tao Wei; Songtao Zhang; Linlin Hou; Jinfeng Ni; Duohong Sheng; Yulong Shen (Extremophiles, 2011)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Determination of Phthalate Esters in Soil Samples by Microwave Assisted Extraction and High Performance Liquid Chromatography - Pei Liang; Linlin Zhang; Lili Peng; Qian Li; Ehong Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

Multi-path PALSAR interferometric observations of the 2008 magnitude 8.0 Wenchuan Earthquake - Kui Zhang; Alex Hay-Man Ng; Linlin Ge; Yusen Dong; Chris Rizos (International Journal of Remote Sensing, 2010)

Isolation of two novel complete Ty1-copia retrotransposons from apple and demonstration of use of derived S-SAP markers for distinguishing bud sports of Malus domestica cv. Fuji - Guiling Zhao; Hongyan Dai; Linlin Chang; Yue Ma; Haiyue Sun; Ping He; Zhihong Zhang (Tree Genetics & Genomes, 2010)

Isolation of DNA-methyltransferase genes from strawberry (Fragaria × ananassa Duch.) and their expression in relation to micropropagation - Linlin Chang; Zhihong Zhang; Baiming Han; He Li; Hongyan Dai; Ping He; Hongzhe Tian (Plant Cell Reports, 2009)

MicroRNA expression profiles in conventional and micropropagated strawberry (Fragaria × ananassa Duch.) plants - He Li; Zhihong Zhang; Feifei Huang; Linlin Chang; Yue Ma (Plant Cell Reports, 2009)

The expression of analgesic-antitumor peptide (AGAP) from Chinese Buthus martensii Karsch in transgenic tobacco and tomato - Linlin Lai; Tingting Huang; Yi Wang; Yanfeng Liu; Jinghai Zhang; Yongbo Song (Molecular Biology Reports, 2009)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

A diagnostic study of heavy rainfall in karachi due to merging of a mesoscale low and a diffused tropical depression during South Asian summer monsoon - Ghulam Rasul; Qamar-uz-Zaman Chaudhry; Zhao Sixiong; Zeng Qingcun; Qi Linlin; Zhang Gaoying (Advances in Atmospheric Sciences, 2005)

An analysis of a meso-β system in a mei-yu front using the intensive observation data during CHeRES 2002 - Sun Jianhua; Zhang Xiaoling; Qi Linlin; Zhao Sixiong (Advances in Atmospheric Sciences, 2005)